Optical adhesive sheet

By using an optical adhesive sheet containing a base polymer, a photopolymerizable multifunctional compound and a photopolymerization initiator, the problem of insufficient follow-up of the optical adhesive sheet in the prior art is solved, and good in the bonding process is achieved Height difference follow-up and joint reliability.

CN119432248APending Publication Date: 2025-02-14NITTO DENKO CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411055786.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-08-04
Filing Date
2024-08-02
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

When the existing optical adhesive sheet is bonded to the surface with the printing layer of the protective glass, the height difference is insufficient, resulting in bubbles forming during the bonding process, affecting the bonding reliability.

Method used

Using an optical adhesive sheet containing a base polymer, a photopolymerizable multifunctional compound and a photopolymerization initiator, the height difference d can be followed by at least 50 μm in the height difference follow-up test, and the height difference d can be followed by relative to the adhesive sheet. The ratio of thickness D is 0.4 or more and 0.8 or less, and the adhesive strength is maintained at 1.5 MPa or more during the pulling test.

Benefits of technology

Good height difference following during the bonding process is achieved, bubble formation is avoided, and high bonding reliability is maintained after bonding.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119432248A_ABST
    Figure CN119432248A_ABST
Patent Text Reader

Abstract

The invention relates to an optical adhesive sheet. This adhesive sheet (10) contains a base polymer, a photopolymerizable polyfunctional compound, and a photopolymerization initiator. The adhesive sheet (10) has at least one followable height difference d of 50 [mu] m or more in a predetermined height difference followability test, and the ratio of the followable height difference d to the thickness D of the adhesive sheet (10) is 0.4-0.8 (inclusive). The adhesive sheet (10) has an adhesive strength (B1) of 1.5 MPa or more in a predetermined first tensile test.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an optical adhesive sheet. Background Art

[0002] The display panel has, for example, a laminated structure including components such as a pixel panel, a polarizing film, and a protective glass. In the manufacturing process of the display panel, in order to bond the components included in the laminated structure to each other, for example, an optically transparent adhesive sheet (optical adhesive sheet) is used. The optical adhesive sheet used for display panels is described, for example, in the following patent document 1.

[0003] Prior art literature

[0004] Patent Literature

[0005] Patent Document 1: Japanese Patent Application Publication No. 2010-97070 Summary of the invention

[0006] Problems to be solved by the invention

[0007] The stacked structure of the display panel includes a component with a surface height difference. For example, a decorative or shading printed layer is provided at the edge of the surface on the pixel panel side of the protective glass. The printed layer is, for example, provided on the entire edge of the protective glass. The printed layer has a specified thickness. Therefore, there is a height difference (printing height difference) between the surface of the protective glass and the surface of the printed layer on the pixel panel side of the protective glass. Therefore, the optical adhesive sheet used for display panels requires flexibility (height difference tracking property) to the extent that it can follow the printing height difference. Insufficient height difference tracking property of the optical adhesive sheet, for example, leads to the formation of bubbles along the printed layer between the optical adhesive sheet with a printed layer attached to the surface of the protective glass and the protective glass, which is undesirable.

[0008] From the viewpoint of level difference followability, the optical adhesive sheet is preferably soft. However, the softer the conventional optical adhesive sheet is, the lower the bonding reliability after bonding adherends with the optical adhesive sheet.

[0009] The present invention provides an optical adhesive sheet suitable for achieving both level followability and bonding reliability.

[0010] Means used to solve problems

[0011] The present invention [1] includes an optical adhesive sheet, wherein the optical adhesive sheet comprises a base polymer, a photopolymerizable multifunctional compound and a photopolymerization initiator, the optical adhesive sheet has at least one followable height difference d of 50 μm or more in the height difference followability test described below, and the ratio of the followable height difference d to the thickness D of the optical adhesive sheet is greater than 0.4 and less than 0.8, and the adhesive strength B1 in the first pulling test described below is greater than 1.5 MPa.

[0012] Height difference tracking test:

[0013] First, a glass plate (length 100 mm×width 50 mm) having a first surface and a second surface opposite to the first surface, a polyethylene terephthalate film (length 100 mm×width 50 mm), and a sample sheet of the optical adhesive sheet (length 75 mm×width 45 mm) were prepared. A printed layer having a thickness h of 50 μm or more was formed on the first surface of the glass plate over the entire edge of the glass plate. The printed layer was formed within a range of 15 mm inward from each end of the glass plate in the length direction of the glass plate, and within a range of 5 mm inward from each end of the glass plate in the width direction of the glass plate.

[0014] Next, the first surface side of the glass plate and the polyethylene terephthalate film are bonded in the thickness direction via the sample piece arranged at the center of the glass plate in the length direction and the width direction, thereby obtaining a first bonded body. In the first bonded body, the printed layer is sandwiched between the glass plate and the sample piece within a range of 2.5 mm from the inner end of the printed layer to the outer side.

[0015] Next, the first bonded body was subjected to a heat treatment under the conditions of 50° C., 0.5 MPa, and 15 minutes.

[0016] Next, the cumulative irradiation light dose was 3000 mJ / cm 2 The sample sheet in the first bonded body is photocured by irradiating the sample sheet with ultraviolet light.

[0017] Next, the inside of the inner edge of the printed layer was observed from the polyethylene terephthalate film side of the first bonded body using a digital microscope at an observation magnification of 20. If no air bubbles were observed in the observation range, the thickness h was taken as the followable height difference d.

[0018] First pull test:

[0019] First, the first alkali glass plate and the second alkali glass plate were bonded in the thickness direction via the optical adhesive sheet to obtain a second bonded body. 2 The optical adhesive sheet is photocured by ultraviolet irradiation; then, the second bonded body is heat treated under the conditions of 50°C, 0.5 MPa and 15 minutes; then, the first alkali glass plate and the second alkali glass plate in the second bonded body are pulled toward opposite sides of each other in the thickness direction at 85°C and a pulling speed of 25 mm / min, thereby measuring the adhesive strength B1.

[0020] The present invention [2] includes the optical adhesive sheet according to the above [1], which has an adhesive strength B2 in the second pull test described below, and a ratio of the adhesive strength B2 to the adhesive strength B1 is 2.0 or more and 3.5 or less.

[0021] Second pulling test:

[0022] First, the first alkali glass plate and the second alkali glass plate were bonded in the thickness direction via the optical adhesive sheet to obtain a third bonded body. 2 The optical adhesive sheet is photocured by ultraviolet irradiation; then, the third bonded body is heat treated under the conditions of 50°C, 0.5 MPa and 15 minutes; then, the first alkali glass plate and the second alkali glass plate in the third bonded body are pulled toward opposite sides of each other in the thickness direction under the conditions of 25°C and a pulling speed of 25 mm / min, thereby measuring the adhesive strength B2.

[0023] The present invention [3] includes the optical adhesive sheet according to [1] or [2], which has an adhesive strength B3 in the third pulling test described below, and a ratio of the adhesive strength B3 to the adhesive strength B1 is 3.0 or more and 4.2 or less.

[0024] The third pulling test:

[0025] First, the first alkali glass plate and the second alkali glass plate were bonded in the thickness direction via the optical adhesive sheet to obtain a fourth bonded body. 2 The optical adhesive sheet was photocured by ultraviolet irradiation. Then, the fourth bonded body was heat treated at 50°C, 0.5 MPa and 15 minutes. Then, the first alkali glass plate and the second alkali glass plate in the fourth bonded body were pulled toward opposite sides in the thickness direction at -20°C and a pulling speed of 25 mm / min to measure the adhesive strength B3.

[0026] The present invention [4] comprises the optical adhesive sheet according to any one of [1] to [3] above, wherein the thickness D is 80 μm or more.

[0027] Effects of the Invention

[0028] As described above, the optical adhesive sheet of the present invention comprises a base polymer, a photopolymerizable multifunctional compound and a photopolymerization initiator. Therefore, the optical adhesive sheet can be attached to the surface with a height difference of the adherend in a soft state before photocuring (photocuring can be performed after laminating). Moreover, the optical adhesive sheet before photocuring has at least one followable height difference d of more than 50 μm in the height difference tracking test, and the ratio of the followable height difference d to the thickness D of the optical adhesive sheet is more than 0.4 and less than 0.8. Such an optical adhesive sheet is suitable for achieving good height difference tracking in the lamination of an adherend having a surface with a height difference.

[0029] As described above, the optical adhesive sheet of the present invention has an adhesive strength B1 (adhesive strength of the optical adhesive sheet after photocuring) of 1.5 MPa or more in the first pull test. Such an optical adhesive sheet is suitable for achieving good bonding reliability after bonding between adherends.

[0030] Therefore, the optical adhesive sheet of the present invention is suitable for achieving both the ability to follow the level difference of the adherend surface during the bonding between the adherends and the bonding reliability after the bonding between the adherends. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 This is a schematic cross-sectional view of one embodiment of the optical adhesive sheet of the present invention.

[0032] Figure 2 The positional relationship between the glass plate and the adhesive sheet in the laminate used for the evaluation of the step followability in Examples and Comparative Examples is shown.

[0033] Figure 3 The pulling tests (first pulling test, second pulling test, third pulling test) are schematically shown.

[0034] Figure 4 shows Figure 1 An example of a method for producing an optical adhesive sheet is shown. Figure 4A It shows the process of forming the coating film of the adhesive composition, Figure 4B Indicates the basic adhesive sheet forming process, Figure 4C Indicates a peeling process of a release liner, Figure 4D It indicates the process of adding components after supplying the base adhesive sheet. Figure 4E This indicates the step of attaching a release liner to an optical adhesive sheet.

[0035] Figure 5 shows Figure 1 An example of the method of using the optical adhesive sheet shown. Figure 5A It refers to the process of attaching the optical adhesive sheet to the member (adherend). Figure 5B It indicates the process of bonding the components to each other via an optical adhesive sheet. Figure 5C This shows the step of photocuring the optical adhesive sheet between the members.

[0036] Description of symbols

[0037] 10 Adhesive sheet (optical adhesive sheet)

[0038] H thickness direction

[0039] 21, 22 Release liner

[0040] 31 Protective glass

[0041] 32 printing layers

[0042] 33 Components DETAILED DESCRIPTION

[0043] like Figure 1 As shown, the adhesive sheet 10 as one embodiment of the present invention has a sheet shape with a predetermined thickness and extends in a direction (plane direction) perpendicular to the thickness direction H. The adhesive sheet 10 has an adhesive surface 11 and an adhesive surface 12 opposite to the adhesive surface 11 . Figure 1 The following example shows a state where release liners 21 and 22 are attached to the adhesive surfaces 11 and 12 of the adhesive sheet 10. The release liner 21 is in releasable contact with the adhesive surface 11. The release liner 22 is in releasable contact with the adhesive surface 12.

[0044] The adhesive sheet 10 is an optically transparent adhesive sheet (optical adhesive sheet). The adhesive sheet 10 contains a base polymer, a photopolymerizable multifunctional compound (a first photopolymerizable multifunctional compound) and a photopolymerization initiator, and has photocurability. The adhesive sheet 10 is, for example, an optical adhesive sheet disposed in a light-passing portion of a display panel. As display panels, for example, liquid crystal display panels and organic EL display panels can be cited. The display panel has, for example, a laminated structure including components such as a pixel panel, a polarizing film, a touch panel and a protective glass. The adhesive sheet 10 is used, for example, in the manufacturing process of a display panel to bond the components contained in the laminated structure to each other.

[0045] The adhesive sheet 10 has at least one followable step d of 50 μm or more in the step followability test described below, and the ratio (d / D) of the followable step d to the thickness D of the adhesive sheet 10 is 0.4 or more and 0.8 or less.

[0046] Height difference tracking test:

[0047] First, a glass plate (length 100 mm×width 50 mm) having a first surface and a second surface opposite to the first surface, a polyethylene terephthalate film (length 100 mm×width 50 mm), and a sample sheet of the adhesive sheet 10 (length 75 mm×width 45 mm) were prepared (first step). A printed layer having a thickness h of 50 μm or more was formed on the first surface of the glass plate over the entire edge of the glass plate. The printed layer was formed within a range of 15 mm inward from each end of the glass plate in the longitudinal direction of the glass plate, and within a range of 5 mm inward from each end of the glass plate in the width direction of the glass plate.

[0048] Next, the first surface side of the glass plate and the polyethylene terephthalate film are bonded in the thickness direction via a sample sheet (adhesive sheet 10) disposed at the center of the glass plate in the longitudinal and width directions to obtain a bonded body (first bonded body) (second step). Figure 2 1 shows the positional relationship between the glass plate 31, the sample sheet 32 ​​of the adhesive sheet 10, and the printed layer 33 in the bonded body. Specifically, the printed layer 33 is formed on the entire edge of the glass plate 31 on one surface in the thickness direction of the glass plate 31. The printed layer 33 is formed within a range of 15 mm from each end of the glass plate 31 in the length direction L1, and within a range of 5 mm from each end of the glass plate 31 in the width direction L2 (within 1 mm). Figure 2 In the figure, hatching is indicated to indicate the printed layer 33). The sample sheet 32 ​​is attached to the center of one side of the glass plate 31 in the thickness direction, and the entire edge of the sheet is in contact with the printed layer 33. That is, the printed layer 33 on the glass plate 31 is sandwiched between the glass plate 31 and the sample sheet 32 ​​within a range of 2.5 mm from the inner end of the printed layer 33 to the outer side.

[0049] Next, the bonded body was subjected to a heat treatment under the conditions of 50° C., 0.5 MPa, and 15 minutes (third step).

[0050] Next, the cumulative irradiation light dose was 3000 mJ / cm 2 The sample piece 32 in the bonded body is photocured by irradiation with ultraviolet rays (the fourth step).

[0051] Next, the inside of the inner edge of the printed layer 33 is observed from the polyethylene terephthalate film side of the bonded body using a digital microscope at an observation magnification of 20 (fifth step). Then, if no bubbles are confirmed within the observation range, the thickness h is taken as the followable height difference d (sixth step). The method of the height difference followability test is more specifically described later in the examples.

[0052] The adhesive strength B1 of the pressure-sensitive adhesive sheet 10 in the first tensile test described below is 1.5 MPa or more.

[0053] First pull test:

[0054] First, the first alkali glass plate and the second alkali glass plate are bonded in the thickness direction via the adhesive sheet 10 to obtain a bonded body (second bonded body). Figure 3 As shown in FIG. 1 , the bonded body W includes a first alkali glass plate 41, an adhesive sheet 10, and a second alkali glass plate 42 in this order in the thickness direction H. The adhesive sheet 10 bonds the first alkali glass plate 41 to the second alkali glass plate. Next, the bonded body W is bonded to the first alkali glass plate 41 by irradiating the light with a cumulative amount of 3000 mJ / cm 2 The adhesive sheet 10 is photocured by ultraviolet irradiation. Next, the joint body W is heat treated at 50°C, 0.5 MPa, and 15 minutes. Next, the first alkali glass plate 41 and the second alkali glass plate 42 in the joint body W are stretched toward opposite sides in the thickness direction at 85°C and a pulling speed of 25 mm / min to measure the adhesive strength B1. The method of the first pulling test is more specifically as described later in the examples.

[0055] As described above, the adhesive sheet 10 includes a base polymer, a first photopolymerizable multifunctional compound, and a photopolymerization initiator. Therefore, the adhesive sheet 10 can be attached to the surface with a height difference of the adherend in a soft state before photocuring (photocuring can be performed after bonding). Moreover, the adhesive sheet 10 before photocuring has at least one followable height difference d of more than 50 μm in the height difference tracking test as described above, and the ratio (d / D) of the followable height difference d relative to the thickness D of the adhesive sheet 10 is greater than 0.4 and less than 0.8. Such an adhesive sheet 10 is suitable for achieving good height difference tracking in the bonding of an adherend with a surface with a height difference.

[0056] Furthermore, as described above, the adhesive strength B1 of the adhesive sheet 10 in the first pull test (adhesive strength of the adhesive sheet 10 after photocuring) is 1.5 MPa or more. Such an adhesive sheet 10 is suitable for achieving good bonding reliability after bonding between adherends (particularly bonding reliability in a high temperature region).

[0057] Therefore, the pressure-sensitive adhesive sheet 10 is suitable for achieving both the ability to follow the height difference of the adherend surface when the adherends are joined together and the reliability of the joining after the adherends are joined together.

[0058] From the perspective of achieving good height difference tracking in the adhesive sheet 10, the ratio (d / D) is preferably 0.45 or more, more preferably 0.48 or more, and further preferably 0.5 or more. From the perspective of suppressing the dents in the adhesive sheet 10 and suppressing the protrusion of the glue, the ratio (d / D) is preferably 0.7 or less, more preferably 0.65 or less. As a method for adjusting the ratio (d / D), for example, the selection of the type of base polymer in the adhesive sheet 10, the adjustment of the molecular weight, the adjustment of the degree of crosslinking, and the adjustment of the amount of compounding can be cited. The selection of the type of base polymer includes the adjustment of the composition of the monomers that form the base polymer.

[0059] From the viewpoint of ensuring the reliability of the joint in the high temperature region after the adhesive sheet 10 is used to bond the adherend, the adhesive strength B1 is preferably 1.7MPa or more, more preferably 1.9MPa or more, and further preferably 2.1MPa or more. The adhesive strength B1 is, for example, 10MPa or less, 7MPa or less, or 5MPa or less. As a method for adjusting the adhesive strength B1, for example, the selection of the type of the base polymer in the adhesive sheet 10, the adjustment of the molecular weight, the adjustment of the degree of crosslinking, and the adjustment of the amount of the compounding can be cited. The selection of the type of the base polymer includes the adjustment of the composition of the monomers forming the base polymer. As a method for adjusting the adhesive strength B1, it can also be cited: the selection of the type of the component other than the base polymer in the adhesive sheet 10, and the adjustment of the amount of the component. As the component, a first photopolymerizable multifunctional compound, a photopolymerization initiator, a silane coupling agent, and an oligomer can be cited. The above adjustment method is also the same for the adhesive strengths B2 and B3 described later.

[0060] From the viewpoint of ensuring the reliability of the bonding in the room temperature region after the adhesive sheet 10 is used to bond the adherends, the adhesive strength B2 in the second pull test of the adhesive sheet 10 is preferably 4.9 MPa or more, more preferably 5.1 MPa or more, and further preferably 5.3 MPa or more. The second pull test is carried out in the same manner as the first pull test, except that the measuring temperature is set to 25°C instead of 85°C. The method of the second pull test is more specifically as described later in relation to the embodiments. The adhesive strength B2 is, for example, less than 15 MPa, less than 12 MPa or less than 10 MPa. In addition, from the viewpoint of ensuring the above-mentioned bonding reliability, the ratio (B2 / B1) of the adhesive strength B2 (25°C) to the adhesive strength B1 (85°C) is preferably 2.0 or more, more preferably 2.2 or more, and (B2 / B1) is preferably 3.5 or less, more preferably 3.2 or less, and further preferably 2.9 or less.

[0061] From the viewpoint of ensuring the reliability of the bonding in the low temperature region after the adhesive sheet 10 is used to bond the adherends, the adhesive strength B3 in the third pull test of the adhesive sheet 10 is preferably 7.7 MPa or more, more preferably 7.9 MPa or more, and further preferably 8.0 MPa or more. The third pull test is carried out in the same manner as the first pull test, except that the measuring temperature is set to -20°C instead of 85°C. The method of the third pull test is more specifically as described later in relation to the embodiments. The adhesive strength B3 is, for example, less than 20 MPa, less than 17 MPa, or less than 15 MPa. In addition, from the viewpoint of ensuring the above-mentioned bonding reliability, the ratio (B3 / B1) of the adhesive strength B3 (-20°C) to the adhesive strength B1 (85°C) is preferably 3.0 or more, more preferably 2.2 or more, and (B3 / B1) is preferably 4.5 or less, more preferably 4.2 or less.

[0062] The base polymer in the adhesive sheet 10 in this embodiment is a photopolymer of a monomer component and a second photopolymerizable multifunctional compound. Photopolymerization refers to a polymerization method in which a polymerization reaction of a polymerizable component is carried out by irradiation with active energy rays such as ultraviolet rays. A photopolymer refers to a product formed by such a polymerization method. The monomer component in this embodiment is a monofunctional monomer. The second photopolymerizable multifunctional compound is a crosslinker in the base polymer. The base polymer is, for example, a photopolymer of a partial polymer (including unreacted monomer components) based on the photopolymerization of the monomer component and a second photopolymerizable multifunctional compound (crosslinker).

[0063] Such a base polymer includes a photopolymerizable polymer (first photopolymerizable polymer) having a crosslinked structure. The crosslinked structure in the first photopolymerizable polymer is a structure in which a linear structure of a unit derived from a monofunctional monomer is crosslinked by a unit derived from a crosslinking agent. The base polymer may include a photopolymerizable polymer (second photopolymerizable polymer) not having such a crosslinked structure. The second photopolymerizable polymer is a polymer of a monofunctional monomer.

[0064] The base polymer is preferably an acrylic polymer. The acrylic polymer is a copolymer containing a polymerizable component of an alkyl (meth)acrylate at a ratio of 50% by mass or more. "(Meth)acrylic acid" means acrylic acid and / or methacrylic acid.

[0065] The alkyl (meth)acrylate is preferably an alkyl (meth)acrylate having an alkyl group having 1 to 20 carbon atoms. The alkyl (meth)acrylate may have a linear or branched alkyl group, or may have a cyclic alkyl group (alicyclic alkyl group).

[0066] Examples of the linear or branched alkyl (meth)acrylate include methyl (meth)acrylate, ethyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, sec-butyl (meth)acrylate, tert-butyl (meth)acrylate, pentyl (meth)acrylate, isopentyl (meth)acrylate, neopentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-octyl (meth)acrylate, isooctyl (meth)acrylate, nonyl (meth)acrylate, isononyl (meth)acrylate, n-decyl (meth)acrylate, and tert-butyl (meth)acrylate. The present invention relates to isodecyl (meth)acrylate, undecyl (meth)acrylate, dodecyl (meth)acrylate (i.e., lauryl (meth)acrylate), tridecyl (meth)acrylate, isotridecyl (meth)acrylate, tetradecyl (meth)acrylate, isotetradecyl (meth)acrylate, pentadecyl (meth)acrylate, hexadecyl (meth)acrylate, heptadecyl (meth)acrylate, octadecyl (meth)acrylate (i.e., stearyl (meth)acrylate), isooctadecyl (meth)acrylate (i.e., isostearyl (meth)acrylate) and nonadecyl (meth)acrylate.

[0067] As the (meth)acrylic acid alkyl ester having an alicyclic alkyl group, for example, cycloalkyl (meth)acrylic acid ester, alkyl (meth)acrylic acid ester having a bicyclic aliphatic hydrocarbon ring, and alkyl (meth)acrylic acid ester having a tricyclic or higher aliphatic hydrocarbon ring can be cited. As the (meth)acrylic acid cycloalkyl ester, for example, cyclopentyl (meth)acrylic acid ester, cyclohexyl (meth)acrylic acid ester, cycloheptyl (meth)acrylic acid ester, and cyclooctyl (meth)acrylic acid ester can be cited. As the (meth)acrylic acid alkyl ester having a bicyclic aliphatic hydrocarbon ring, for example, isobornyl (meth)acrylic acid ester can be cited. As the (meth)acrylic acid alkyl ester having a tricyclic or higher aliphatic hydrocarbon ring, for example, tetrahydrodicyclopentadienyl (meth)acrylate, tetrahydrodicyclopentadienyloxyethyl (meth)acrylate, tetrahydrotricyclopentadienyl (meth)acrylate, 1-adamantyl (meth)acrylate, 2-methyl-2-adamantyl (meth)acrylate, and 2-ethyl-2-adamantyl (meth)acrylate can be cited.

[0068] The (meth)acrylic acid alkyl esters may be used alone or in combination of two or more.

[0069] From the viewpoint of appropriately expressing basic properties such as adhesiveness in the adhesive sheet 10, the proportion of the (meth)acrylic acid alkyl ester in the monomer component is preferably 60% by mass or more, more preferably 70% by mass or more, and further preferably 75% by mass or more. This proportion is, for example, 99.9% by mass or less, 99.5% by mass or less, or 99% by mass or less.

[0070] The monomer component may include a copolymerizable monomer that can be copolymerized with the (meth)acrylic acid alkyl ester. As the copolymerizable monomer, for example, a polar group-containing monomer may be cited. As the polar group-containing monomer, for example, a hydroxyl group-containing monomer, a carboxyl group-containing monomer, and a monomer having a nitrogen atom-containing ring may be cited. The polar group-containing monomer contributes to the modification of the acrylic polymer such as ensuring the cohesive force of the acrylic polymer.

[0071] Examples of the hydroxyl-containing monomer include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 8-hydroxyoctyl (meth)acrylate, 10-hydroxydecyl (meth)acrylate, and 12-hydroxylauryl (meth)acrylate. The hydroxyl-containing monomer is preferably at least one selected from the group consisting of 2-hydroxyethyl acrylate and 4-hydroxybutyl acrylate.

[0072] From the viewpoint of ensuring the cohesive force of the adhesive sheet 10, the proportion of the hydroxyl-containing monomer in the monomer component is preferably 1% by mass or more, more preferably 5% by mass or more, and further preferably 8% by mass or more. From the viewpoint of adjusting the polarity of the acrylic polymer (related to the compatibility of various additive components in the adhesive sheet 10 with the acrylic polymer), the proportion is preferably 30% by mass or less, more preferably 20% by mass or less, and further preferably 15% by mass or less.

[0073] Examples of the carboxyl group-containing monomer include acrylic acid, methacrylic acid, carboxyethyl acrylate, carboxypentyl acrylate, itaconic acid, maleic acid, fumaric acid, crotonic acid, and isocrotonic acid.

[0074] From the viewpoint of ensuring the cohesive force of the adhesive sheet 10 and the adhesion of the adhesive sheet 10 to the adherend, the proportion of the carboxyl group-containing monomer in the polymerizable component is preferably 1% by mass or more, more preferably 3% by mass or more, and further preferably 5% by mass or more. From the viewpoint of adjusting the glass transition temperature of the acrylic polymer and avoiding the risk of acid corrosion on the adherend, the proportion is preferably 20% by mass or less, and more preferably 10% by mass or less.

[0075] Examples of the monomer having a nitrogen atom-containing ring include N-vinyl-2-pyrrolidone, N-methylvinylpyrrolidone, N-vinylpyridine, N-vinylpiperidone, N-vinylpyrimidine, N-vinylpiperazine, N-vinylpyrazine, N-vinylpyrrole, N-vinylimidazole, N-vinyl oxadiazole, N-(meth)acryloyl-2-pyrrolidone, N-(meth)acryloylpiperidine, N-(meth)acryloylpyrrolidine, N-vinylmorpholine, N-vinyl-3-morpholine, N-vinyl-2-caprolactam, N-vinyl-1,3- Oxazine-2-one, N-vinyl-3,5-morpholinedione, N-vinylpyrazole, N-vinyliso The monomer having a nitrogen atom-containing ring is preferably at least one selected from the group consisting of N-vinyl-2-pyrrolidone and acryloylmorpholine.

[0076] From the perspective of ensuring the cohesive force of the adhesive sheet and the adhesion of the adhesive sheet to the adherend, the proportion of the monomer having a nitrogen atom ring in the polymerizable component is preferably 1% by mass or more, more preferably 5% by mass or more, and further preferably 8% by mass or more. From the perspective of adjusting the glass transition temperature of the acrylic polymer and adjusting the polarity of the acrylic polymer (related to the compatibility of various additive components in the adhesive sheet with the acrylic polymer), the proportion is preferably 30% by mass or less, and more preferably 20% by mass or less.

[0077] The monomer component preferably comprises a monomer (high Me monomer) having a molecular weight Me between entanglement points of a homopolymer of more than 30,000. That is, the base polymer is preferably a monomer component of a monomer having a molecular weight Me between entanglement points of a homopolymer of more than 30,000 and a photopolymer of a second photopolymerizable multifunctional compound. Such a base polymer has a low degree of entanglement compared to a polymer of the same polymer as a weight average molecular weight and a degree of crosslinking and does not contain a monomer having a molecular weight Me between entanglement points of more than 30,000, and therefore has a high degree of flexibility. That is, the base polymer is suitable for taking into account flexibility and high molecular weight / high degree of crosslinking. The high flexibility of the base polymer contributes to achieving good height difference tracking in the adhesive sheet 10 before photocuring. The high molecular weight and degree of crosslinking of the base polymer contribute to achieving good bonding reliability in the adhesive sheet 10 after photocuring that is bonded between adherends.

[0078] Examples of high Me monomers include alkyl (meth)acrylates having Me of 30,000 or more and copolymerizable monomers having Me of 30,000 or more that can be copolymerized with alkyl (meth)acrylates. Examples of alkyl (meth)acrylates having Me of 30,000 or more include alkyl (meth)acrylates having a linear alkyl group (linear alkyl (meth)acrylates), alkyl (meth)acrylates having a branched alkyl group (branched alkyl (meth)acrylates), and alkyl (meth)acrylates having an alicyclic alkyl group (alicyclic alkyl (meth)acrylates). Examples of copolymerizable monomers having Me of 30,000 or more include aromatic ring-containing monomers.

[0079] The high Me monomer is preferably at least one selected from the group consisting of linear alkyl (meth)acrylates, branched alkyl (meth)acrylates, alicyclic alkyl (meth)acrylates, and aromatic ring-containing monomers.

[0080] Examples of linear alkyl (meth)acrylates as high Me monomers include hexyl methacrylate (Me is 33800), n-octyl acrylate (Me is 39400), n-octyl methacrylate (Me is 47100), n-decyl methacrylate (Me is 60900), lauryl acrylate (Me is 39000), lauryl methacrylate (Me is 80100), n-tridecyl methacrylate (Me is 89200), n-octadecyl acrylate (Me is 14700), and n-octadecyl methacrylate (Me is 215000). Examples of branched alkyl (meth)acrylates as high Me monomers include 2-ethylhexyl acrylate (Me is 39000) and isooctadecyl acrylate (Me is 14700). Examples of alicyclic alkyl (meth)acrylates as high Me monomers include cyclohexyl methacrylate (Me is 33900) and 4-tert-butylcyclohexyl methacrylate (Me is 48400). As the aromatic ring-containing monomer of the high Me monomer, for example, benzyl acrylate (Me is 36000), phenyl methacrylate (Me is 44300), 4-tert-butylphenyl methacrylate (Me is 69700), 4-chlorophenyl acrylate (Me is 63000), 4-chlorophenyl methacrylate (Me is 55100), 4-biphenyl methacrylate (Me is 96000) and triphenylmethyl methacrylate (Me is 203000). As the high Me monomer, 2-cyanoethyl acrylate (Me is 30000) can be mentioned. The method for measuring the molecular weight between entanglement points is described in, for example, "Collection of Polymer Papers" (Vol. 52, No. 3, pp. 187-193, March, 1995) and "Polymer Engineering & Science" (Vol. 30, No. 13, pp. 753-761).

[0081] From the viewpoint of taking into account both the followability of the height difference of the adherend surface when the adhesive sheet 10 before photocuring is bonded to the adherend and the bonding reliability between the adherends of the adhesive sheet 10 after photocuring, the molecular weight Me between the entanglement points of the high Me monomer is preferably 35,000 or more, more preferably 38,000 or more. In addition, the molecular weight Me between the entanglement points of the high Me monomer is preferably 300,000 or less, more preferably 250,000 or less, and further preferably 200,000 or less.

[0082] From the viewpoint of taking into account both the above-mentioned height difference tracking property and the bonding reliability, the proportion of high Me monomers in the monomer component is preferably 5 mass % or more, more preferably 8 mass % or more, and further preferably 10 mass % or more. In addition, the proportion of high Me monomers in the monomer component is preferably 50 mass % or less, more preferably 40 mass % or less, and further preferably 35 mass % or less.

[0083] The monomer component may include a monomer (low Me monomer) having a molecular weight Me between entanglement points of a homopolymer of less than 30000. From the viewpoint of appropriately exhibiting basic properties such as adhesiveness of the adhesive sheet 10, the molecular weight Me between entanglement points of the low Me monomer is preferably 10000 or more, more preferably 14000 or more, and the molecular weight Me between entanglement points of the low Me monomer is preferably less than 30000, more preferably 25000 or less, further preferably 20000 or less, and further preferably 17000 or less.

[0084] From the viewpoint of taking into account both the above-mentioned height difference tracking property and the bonding reliability, the proportion of low Me monomers in the monomer component is preferably 50 mass % or more, more preferably 60 mass % or more, and further preferably 65 mass % or more. In addition, the proportion of low Me monomers in the monomer component is preferably 95 mass % or less, more preferably 92 mass % or less, and further preferably 90 mass % or less.

[0085] The monomer component preferably includes an alkyl (meth)acrylate as a high Me monomer (for example, selected from the above-mentioned alkyl (meth)acrylates), an alkyl (meth)acrylate as a low Me monomer, a monomer having a nitrogen atom ring, and a hydroxyl-containing monomer. The alkyl (meth)acrylate as a high Me monomer is preferably an alkyl (meth)acrylate having 7 to 15 carbon atoms. The alkyl (meth)acrylate as a low Me monomer is preferably an alkyl (meth)acrylate having 1 to 6 carbon atoms. The monomer component more preferably includes 2-ethylhexyl acrylate (high Me monomer), n-butyl acrylate (low Me monomer), N-vinyl-2-pyrrolidone (NVP), acryloylmorpholine (ACMO) and 4-hydroxybutyl acrylate (4HBA).

[0086] As the second photopolymerizable polyfunctional compound (crosslinking agent), for example, polyfunctional oligomers and polyfunctional monomers can be cited.

[0087] Examples of the multifunctional oligomer include urethane acrylate oligomers (oligomers having a urethane skeleton and two or more acryloyl groups), epoxy acrylate oligomers (oligomers having an epoxy skeleton and two or more acryloyl groups), and polysiloxane acrylate oligomers (oligomers having a siloxane skeleton and two or more acryloyl groups). Examples of commercially available urethane acrylate oligomers include ArtResin UN-333, UN-350, UN-353, UN-5500, and UN-5590 manufactured by Negami Industries.

[0088] From the viewpoint of compatibility between the base polymer and the multifunctional oligomer, the weight average molecular weight (Mw) of the multifunctional oligomer is preferably 5000 or more, and the weight average molecular weight (Mw) of the multifunctional oligomer is preferably 20000 or less, and more preferably 15000 or less. The weight average molecular weight is measured by gel permeation chromatography (GPC) and calculated by polystyrene conversion.

[0089] As the multifunctional monomer, for example, a multifunctional (meth)acrylate containing two or more ethylenically unsaturated double bonds in one molecule can be cited. As the multifunctional monomer, from the viewpoint of easily introducing a crosslinking structure by photopolymerization, a multifunctional (meth)acrylate is preferred. As the multifunctional (meth)acrylate, a multifunctional (meth)acrylate described later with respect to the first photopolymerizable multifunctional compound can be cited.

[0090] The second photopolymerizable polyfunctional compound may be used alone or in combination of two or more. The second photopolymerizable polyfunctional compound is preferably a polyfunctional oligomer, more preferably a urethane acrylate oligomer.

[0091] From the viewpoint of achieving good bonding reliability in the adhesive sheet 10 after photocuring between the adherends, the amount of the second photopolymerizable multifunctional compound is preferably 0.1 parts by mass or more, more preferably 0.3 parts by mass or more, and further preferably 0.5 parts by mass or more, relative to 100 parts by mass of the monomer component. From the viewpoint of ensuring flexibility in the adhesive sheet 10 before photocuring and achieving good level difference tracking, the amount of the second photopolymerizable multifunctional compound is preferably 2.0 parts by mass or less, more preferably 1.0 parts by mass or less, and further preferably 0.8 parts by mass or less, relative to 100 parts by mass of the monomer component.

[0092] The base polymer can be formed by photopolymerizing a polymerizable component containing the above-mentioned monomer component (monofunctional monomer) and a second photopolymerizable multifunctional compound. As photopolymerization, for example, photopolymerization using ultraviolet irradiation can be cited. The polymerizable components (monofunctional monomer, second photopolymerizable multifunctional compound) can be polymerized at one time or in multiple steps. In the multi-step polymerization method, first, the monofunctional monomer is polymerized (prepolymerization) to prepare a prepolymer composition containing a partial polymer (a mixture of a polymer with a low degree of polymerization and unreacted monofunctional monomers). Then, after adding the second photopolymerizable multifunctional compound as a crosslinking agent to the prepolymer composition, a polymerization reaction (main polymerization) is carried out in the reaction system containing the partial polymer and the second photopolymerizable multifunctional compound. As an initiator for polymerization, a photopolymerization initiator is used.

[0093] Examples of the photopolymerization initiator include a radical photopolymerization initiator, a cationic photopolymerization initiator, and an anionic photopolymerization initiator.

[0094] Examples of free radical photopolymerization initiators include acylphosphine oxide photopolymerization initiators, benzoin ether photopolymerization initiators, acetophenone photopolymerization initiators, α-ketol photopolymerization initiators, aromatic sulfonyl chloride photopolymerization initiators, photoactive oxime photopolymerization initiators, benzoin photopolymerization initiators, benzyl photopolymerization initiators, benzophenone photopolymerization initiators, ketal photopolymerization initiators, and thioxanthone photopolymerization initiators.

[0095] Examples of the acylphosphine oxide photopolymerization initiator include bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, bis(2,4,6-trimethylbenzoyl)-2,4-di-n-butoxyphenylphosphine oxide, 2,4,6-trimethylbenzoyldiphenylphosphine oxide, and bis(2,6-dimethoxybenzoyl)-2,4,4-trimethylpentylphosphine oxide. Examples of the benzoin ether photopolymerization initiator include benzoin methyl ether, benzoin ethyl ether, benzoin propyl ether, benzoin isopropyl ether, benzoin isobutyl ether, and 2,2-dimethoxy-2-phenylacetophenone. Examples of the acetophenone photopolymerization initiator include 2,2-diethoxyacetophenone, 1-hydroxycyclohexylphenyl ketone, 4-phenoxydichloroacetophenone, and 4-(tert-butyl)dichloroacetophenone. Examples of α-ketol photopolymerization initiators include 2-methyl-2-hydroxypropiophenone and 1-[4-(2-hydroxyethyl)phenyl]-2-methylpropane-1-one. Examples of aromatic sulfonyl chloride photopolymerization initiators include 2-naphthalenesulfonyl chloride. Examples of photoactive oxime photopolymerization initiators include 1-phenyl-1,1-propanedione-2-(O-ethoxycarbonyl)-oxime. Examples of benzoin photopolymerization initiators include benzoin. Examples of benzil photopolymerization initiators include benzil. Examples of benzophenone photopolymerization initiators include benzophenone, benzoylbenzoic acid, 3,3'-dimethyl-4-methoxybenzophenone and polyvinylbenzophenone. Examples of ketal photopolymerization initiators include benzil dimethyl ketal. As thioxanthone photopolymerization initiator, for example, thioxanthone, 2-chlorothioxanthone, 2-methylthioxanthone, 2,4-dimethylthioxanthone, isopropylthioxanthone, 2,4-diisopropylthioxanthone and dodecylthioxanthone can be listed. The photopolymerization initiator can be used alone or in combination of two or more. The photopolymerization initiator is preferably at least one selected from the group consisting of bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, 2,2-dimethoxy-2-phenylacetophenone and 1-hydroxycyclohexylphenyl ketone.

[0096] The amount of the photopolymerization initiator (first photopolymerization initiator) used in the prepolymerization (the total amount of the photopolymerization initiators when multiple photopolymerization initiators are used) is, for example, 0.02 parts by mass or more, preferably 0.04 parts by mass or more, more preferably 0.06 parts by mass or more, and, for example, 1 part by mass or less, preferably 0.5 parts by mass or less, more preferably 0.2 parts by mass or less, and further preferably 0.1 parts by mass or less, relative to 100 parts by mass of the monomer component. The amount of the photopolymerization initiator (second photopolymerization initiator) used in the main polymerization (the total amount of the photopolymerization initiators when multiple photopolymerization initiators are used) is, for example, 0.1 parts by mass or more, preferably 0.2 parts by mass or more, more preferably 0.3 parts by mass or more, and, for example, 2 parts by mass or less, preferably 1 part by mass or less, and more preferably 0.8 parts by mass or less.

[0097] From the viewpoint of ensuring the cohesive force of the adhesive sheet 10, the weight average molecular weight (Mw) of the base polymer is preferably 500,000 or more, more preferably 650,000 or more, and more preferably 800,000 or more. From the viewpoint of ensuring the height difference followability of the adhesive sheet 10, the weight average molecular weight of the base polymer is preferably 1.2 million or less, more preferably 1 million or less, and more preferably 800,000 or less. The weight average molecular weight of the base polymer is measured by gel permeation chromatography (GPC) and calculated by polystyrene conversion. The determination method of the Mw of the base polymer is specifically as described in the following embodiments.

[0098] From the viewpoint of ensuring sufficient softness in the adhesive sheet 10 before photocuring, the glass transition temperature (Tg) of the base polymer is preferably 0°C or lower, more preferably -20°C or lower, further preferably -40°C or lower, and further preferably -45°C or lower. The glass transition temperature is, for example, -80°C or higher.

[0099] Regarding the glass transition temperature of the base polymer, the glass transition temperature (theoretical value) obtained based on the following Fox formula can be used. The Fox formula is a relationship between the glass transition temperature Tg of a polymer and the glass transition temperature Tgi of a homopolymer of a monomer constituting the polymer. In the following Fox formula, Tg represents the glass transition temperature (°C) of the polymer, Wi represents the weight fraction of the monomer i constituting the polymer, and Tgi represents the glass transition temperature (°C) of the homopolymer formed by monomer i. Regarding the glass transition temperature of a homopolymer, a literature value can be used. For example, the glass transition temperatures of various homopolymers are listed in "Polymer Handbook" (4th edition, John Wiley & Sons, Inc., 1999). On the other hand, the glass transition temperature of a homopolymer of a monomer can also be obtained by the method specifically described in Japanese Patent Gazette No. 2007-51271.

[0100] Fox formula 1 / (273+Tg)=Σ[Wi / (273+Tgi)]

[0101] Examples of the first photopolymerizable polyfunctional compound in the adhesive sheet 10 include polyfunctional monomers and polyfunctional oligomers.

[0102] Examples of the polyfunctional monomer include polyfunctional (meth)acrylates, and examples of the polyfunctional (meth)acrylates include difunctional (meth)acrylates, trifunctional (meth)acrylates, and tetrafunctional or higher polyfunctional (meth)acrylates.

[0103] Examples of the difunctional (meth)acrylate include ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, tetraethylene glycol dimethacrylate, 1,6-hexanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, glycerol di(meth)acrylate, neopentyl glycol di(meth)acrylate, stearic acid-modified pentaerythritol di(meth)acrylate, dihydrodicyclopentadienyl acrylate, di(meth)acryloyl isocyanurate, and ethoxylated bisphenol A diacrylate (BPAEODE).

[0104] Examples of the trifunctional (meth)acrylate include trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, and tri(acryloyloxyethyl)isocyanurate.

[0105] Examples of the tetrafunctional or higher polyfunctional (meth)acrylate include di(trimethylolpropane)tetra(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol monohydroxy penta(meth)acrylate, alkyl-modified dipentaerythritol pentaacrylate, and dipentaerythritol hexa(meth)acrylate.

[0106] As the polyfunctional oligomer, for example, the polyfunctional oligomer described above with respect to the second photopolymerizable polyfunctional compound can be cited.

[0107] The first photopolymerizable multifunctional compound may be used alone or in combination of two or more.

[0108] The first photopolymerizable multifunctional compound is preferably at least one selected from the group consisting of difunctional (meth)acrylates and trifunctional (meth)acrylates, and more preferably at least one selected from the group consisting of BPAEODE and trimethylolpropane triacrylate (TMPTA).

[0109] From the viewpoint of ensuring good bonding reliability after photocuring in the adhesive sheet 10, the content of the first photopolymerizable multifunctional compound in the adhesive sheet 10 (the total content when the adhesive sheet 10 contains a plurality of first photopolymerizable multifunctional compounds) is preferably 0.5 parts by mass or more, more preferably 2 parts by mass or more, and further preferably 5 parts by mass or more, relative to 100 parts by mass of the base polymer. From the viewpoint of ensuring good bonding reliability after photocuring in the adhesive sheet 10, the content of the first photopolymerizable multifunctional compound in the adhesive sheet 10 is preferably 20 parts by mass or less, more preferably 15 parts by mass or less, and further preferably 10 parts by mass or less, relative to 100 parts by mass of the base polymer.

[0110] Examples of the photopolymerization initiator (third photopolymerization initiator) in the pressure-sensitive adhesive sheet 10 include radical photopolymerization initiators, cationic photopolymerization initiators, and anionic photopolymerization initiators. Specifically, examples include the photopolymerization initiators described above for photopolymerization of the base polymer.

[0111] From the viewpoint of ensuring good photocurability in the adhesive sheet 10, the content of the photopolymerization initiator in the adhesive sheet 10 is preferably 0.1 parts by mass or more, more preferably 0.2 parts by mass or more, and further preferably 0.25 parts by mass or more, relative to 100 parts by mass of the base polymer. In addition, the content of the photopolymerization initiator in the adhesive sheet 10 is preferably 3 parts by mass or less, more preferably 1.5 parts by mass or less, and further preferably 0.5 parts by mass or less.

[0112] The pressure-sensitive adhesive sheet 10 may contain other components. Examples of other components include oligomers, ultraviolet absorbers, antioxidants, silane coupling agents, and rust inhibitors.

[0113] When the base polymer is an acrylic polymer, the oligomer is preferably an acrylic oligomer. The acrylic oligomer is a copolymer containing a monomer component of (meth)acrylic acid ester at a ratio of 50 mass % or more, and has a weight average molecular weight of, for example, 1,000 or more and 30,000 or less.

[0114] The acrylic oligomer is preferably a polymer containing monomer components of a (meth)acrylic acid alkyl ester having a chain alkyl group (chain alkyl (meth)acrylate) and a (meth)acrylic acid alkyl ester having an alicyclic alkyl group (alicyclic alkyl (meth)acrylate). Specific examples of these (meth)acrylic acid alkyl esters include the above-mentioned (meth)acrylic acid alkyl esters as polymerizable components of the acrylic polymer.

[0115] As the (meth)acrylic acid chain alkyl ester, methyl methacrylate is preferred from the viewpoint of high glass transition temperature and excellent compatibility with the base polymer. As the (meth)acrylic acid alicyclic alkyl ester, tetrahydrodicyclopentadienyl acrylate, tetrahydrodicyclopentadienyl methacrylate, cyclohexyl acrylate and cyclohexyl methacrylate are preferred. That is, the acrylic oligomer is preferably a polymer comprising a monomer component of methyl methacrylate and one or more selected from the group consisting of tetrahydrodicyclopentadienyl acrylate, tetrahydrodicyclopentadienyl methacrylate, cyclohexyl acrylate and cyclohexyl methacrylate.

[0116] The ratio of (meth) acrylic acid alicyclic alkyl ester in the monomer component of acrylic acid oligomer is preferably 10% by mass or more, more preferably 20% by mass or more, and more preferably 30% by mass or more. The ratio is preferably 90% by mass or less, more preferably 80% by mass or less, and more preferably 70% by mass or less. The ratio of (meth) acrylic acid chain alkyl ester in the monomer component of acrylic acid oligomer is preferably 90% by mass or less, more preferably 80% by mass or less, and more preferably 70% by mass or less. The ratio is preferably 10% by mass or more, more preferably 20% by mass or more, and more preferably 30% by mass or more.

[0117] Acrylic oligomers are obtained by polymerizing the monomer components of the acrylic oligomers. Examples of the polymerization method include solution polymerization, bulk polymerization, and emulsion polymerization. Acrylic oligomers are preferably formed by solution polymerization. Examples of solvents in solution polymerization include toluene and ethyl acetate. In the polymerization of acrylic oligomers, a thermal polymerization initiator may be used, and a chain transfer agent may be used for the purpose of regulating the molecular weight. In addition, in the present embodiment, after the acrylic oligomers are formed, the low molecular weight components and the solvent are volatilized and removed from the reaction system such as the reaction solution by heating. Examples of the low molecular weight components include: unreacted monomers, chain transfer agents, thermal polymerization initiators, and their decomposition products (residues).

[0118] Examples of thermal polymerization initiators include azo polymerization initiators and peroxide polymerization initiators. Examples of azo polymerization initiators include 2,2'-azobisisobutyronitrile, 2,2'-azobis(-2-methylbutyronitrile) and 2,2'-azobis(2-methylpropionic acid) dimethyl ester. Examples of peroxide polymerization initiators include dibenzoyl peroxide, tert-butyl peroxymaleate and lauroyl peroxide.

[0119] Examples of the chain transfer agent include α-thioglycerol, dodecyl mercaptan, glycidyl mercaptan, thioglycolic acid, 2-mercaptoethanol, thioglycolic acid, 2-ethylhexyl thioglycolate, 2,3-dimercapto-1-propanol, and α-methylstyrene dimer.

[0120] From the viewpoint of ensuring the adhesive force of the adhesive sheet 10, the weight average molecular weight (Mw) of the oligomer is preferably 1000 or more, more preferably 1500 or more, and further preferably 2000 or more. In addition, the weight average molecular weight (Mw) of the oligomer is preferably 30000 or less, more preferably 10000 or less, and further preferably 8000 or less. The weight average molecular weight of the oligomer is measured by gel permeation chromatography (GPC) and calculated by polystyrene conversion. The determination method of the Mw of the oligomer is specifically described in the following embodiments.

[0121] From the viewpoint of ensuring the adhesive force of the adhesive sheet 10, the content of the oligomer in the adhesive sheet 10 is preferably 0.05 parts by mass or more, more preferably 0.1 parts by mass or more, and further preferably 0.2 parts by mass or more, relative to 100 parts by mass of the base polymer. From the viewpoint of ensuring the transparency of the adhesive sheet 10, the content of the oligomer in the adhesive sheet 10 is preferably 5 parts by mass or less, more preferably 3 parts by mass or less, and further preferably 1 part by mass or less, relative to 100 parts by mass of the base polymer.

[0122] Examples of the ultraviolet absorber include triazine ultraviolet absorbers, benzotriazole ultraviolet absorbers, benzophenone ultraviolet absorbers, salicylate ultraviolet absorbers, and cyanoacrylate ultraviolet absorbers. As the ultraviolet absorber, triazine ultraviolet absorbers are preferred from the viewpoint of high absorption of ultraviolet rays in the range of 320 nm to 370 nm in wavelength and excellent compatibility with acrylic polymers. The ultraviolet absorbers may be used alone or in combination of two or more.

[0123] Examples of commercially available triazine-based ultraviolet absorbers include bis-ethylhexyloxyphenol methoxyphenyl triazine (trade name "Tinosorb S", manufactured by BASF), a reaction product of 2-(4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine-2-yl)-5-hydroxyphenyl and [(alkoxy)methyl]oxirane (trade name "TINUVIN 400", manufactured by BASF), a reaction product of 2-(2,4-dihydroxyphenyl)-4,6-bis-(2,4-dimethylphenyl)-1,3,5-triazine and (2-ethylhexyl)-glycidate (trade name "TINUVIN 405", manufactured by BASF), (2,4-bis[2-hydroxy-4-butoxyphenyl]-6-(2,4-dibutoxyphenyl)-1,3,5-triazine (trade name "TINUVIN 460", manufactured by BASF), 2-(4,6-diphenyl-1,3,5-triazine-2-yl)-5-[(hexyl)oxy]-phenol (trade name "TINUVIN 577", manufactured by BASF), 2-(2-hydroxy-4-[1-octyloxycarbonylethoxy]phenyl)-4,6-bis(4-phenylphenyl)-1,3,5-triazine (trade name "TINUVIN 479", manufactured by BASF) and 2-(4,6-diphenyl-1,3,5-triazine-2-yl)-5-[2-(2-ethylhexanoyloxy)ethoxy]-phenol ("ADK STAB LA-46", manufactured by ADEKA).

[0124] The content of the ultraviolet absorber in the adhesive sheet 10 is preferably 0.5 parts by mass or more, more preferably 1 part by mass or more, and further preferably 3 parts by mass or more, relative to 100 parts by mass of the base polymer. In addition, the content of the ultraviolet absorber in the adhesive sheet 10 is preferably 15 parts by mass or less, more preferably 10 parts by mass or less, and further preferably 8 parts by mass or less. Such a configuration is preferred from the viewpoint of achieving both the ultraviolet shielding function of the adhesive sheet 10 for protecting the device and the photocurability.

[0125] Examples of the antioxidant include phenolic antioxidants, phosphorus-containing antioxidants, sulfur-containing antioxidants, and amine-based antioxidants. The antioxidants may be used alone or in combination of two or more.

[0126] As the antioxidant, a phenolic antioxidant is preferably used, and a hindered phenolic antioxidant is more preferably used. Examples of the hindered phenolic antioxidant include pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] (trade name "Irganox 1010", manufactured by BASF) and octadecyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate (trade name "Irganox 1076", manufactured by BASF).

[0127] The content of the antioxidant in the adhesive sheet 10 is preferably 0.05 parts by mass or more, more preferably 0.1 parts by mass or more, relative to 100 parts by mass of the base polymer, and the content of the antioxidant in the adhesive sheet 10 is preferably 3 parts by mass or less, more preferably 2 parts by mass or less. Such a configuration is preferred from the viewpoint of achieving both the suppression of oxidative degradation of the adhesive sheet 10 and the photocurability.

[0128] As the silane coupling agent, for example, a silane coupling agent containing an epoxy group can be cited. As the silane coupling agent containing an epoxy group, for example, 3-glycidoxydialkyldialkoxysilane and 3-glycidoxyalkyltrialkoxysilane can be cited. As 3-glycidoxydialkyldialkoxysilane, for example, 3-glycidoxypropylmethyldimethoxysilane and 3-glycidoxypropylmethyldiethoxysilane can be cited. As 3-glycidoxyalkyltrialkoxysilane, for example, 3-glycidoxypropyltrimethoxysilane and 3-glycidoxypropyltriethoxysilane can be cited. As the silane coupling agent, 3-glycidoxyalkyltrialkoxysilane is preferably used, and 3-glycidoxypropyltrimethoxysilane is more preferably used. The silane coupling agent can be used alone or in combination of two or more. The content of the silane coupling agent in the adhesive sheet 10 is preferably 0.1 parts by mass or more, more preferably 0.2 parts by mass or more, relative to 100 parts by mass of the base polymer, and is preferably 5 parts by mass or less, more preferably 3 parts by mass or less.

[0129] Examples of the rust inhibitor include benzotriazole compounds, such as 1,2,3-benzotriazole, 5-methylbenzotriazole, 4-methylbenzotriazole, and carboxybenzotriazole.

[0130] The content of the rust inhibitor in the adhesive sheet 10 is preferably 0.05 parts by mass or more, more preferably 0.1 parts by mass or more, and further preferably 0.15 parts by mass or more, relative to 100 parts by mass of the base polymer. In addition, the content of the rust inhibitor in the adhesive sheet 10 is preferably 2 parts by mass or less, more preferably 1 part by mass or less, and further preferably 0.5 parts by mass or less.

[0131] From the perspective of both sufficient adhesion to the adherend and height difference tracking, the thickness of the adhesive sheet 10 is preferably 80 μm or more, more preferably 90 μm or more, and further preferably 95 μm or more. From the perspective of the operability and ease of cutting of the adhesive sheet 10, the thickness of the adhesive sheet 10 is preferably 500 μm or less, more preferably 400 μm or less, further preferably 300 μm or less, further preferably 200 μm or less, and further preferably 150 μm or less.

[0132] The adhesive sheet 10 preferably has a light transmittance R1 of 10% or less at a wavelength of 380nm, and a light transmittance R2 of 85% or more at a wavelength of 420nm. Such a configuration is preferred for ensuring the transparency required for the display panel application while ensuring the protective function of the display panel obtained by blocking ultraviolet rays in the adhesive sheet 10. From the viewpoint of ensuring the protective function of the adhesive sheet 10, the light transmittance R1 is preferably 8% or less, more preferably 6% or less, and further preferably 5% or less. The light transmittance R1 is, for example, 0.1% or more. From the viewpoint of ensuring the transparency of the adhesive sheet 10, the light transmittance R2 is preferably 87% or more, more preferably 89% or more, and further preferably 90.5% or more. The light transmittance R2 is, for example, 99% or less. Specifically, the method for measuring the light transmittances R1 and R2 is as described later in the embodiments.

[0133] From the perspective of ensuring the drop impact resistance (impact mitigation) after bonding between adherends using the adhesive sheet 10, the dielectric loss tangent tanδ of the adhesive sheet 10 at 25°C is preferably 1.2 or more at a frequency of 1000Hz to 10000Hz, more preferably 1.3 or more, and further preferably 1.4 or more. The frequency of 1000Hz to 10000Hz is equivalent to the vibration frequency generated in the collision object due to the collision of the free-falling object. The collision is, for example, the collision of a laminate obtained by bonding adherends using an adhesive sheet to the ground after free fall. Alternatively, the collision is the collision of a free-falling object (metal ball, etc.) with a laminate obtained by bonding adherends using an adhesive sheet. From the perspective of the operability and processability of the adhesive sheet 10, the dielectric loss tangent tanδ of the adhesive sheet 10 at 25°C is preferably 1.8 or less at a frequency of 1000Hz to 10000Hz, more preferably 1.7 or less, and further preferably 1.6 or less. The dielectric loss tangent tanδ of the adhesive sheet can be measured by a dynamic viscoelasticity measuring device. As a dynamic viscoelasticity measuring device, for example, the "Advanced Rheological Expansion System" manufactured by Rheometric Scientific can be used. In the measurement, the measurement mode is set to the shear mode, the strain amount is set to 0.3%, and is set to -50°C to 150°C, and the angular frequency range is set to 0.01rad / second to 100rad / second. The method for measuring the dielectric loss tangent tanδ is specifically as described later in the embodiments. As a method for adjusting the dielectric loss tangent tanδ of the adhesive sheet 10, for example, the selection of the type of base polymer in the adhesive sheet 10, the adjustment of the molecular weight, the adjustment of the degree of crosslinking, and the adjustment of the compounding amount can be listed.

[0134] From the viewpoint of drop impact resistance (impact mitigation) after the adhesive sheet 10 is bonded to an adherend, the dielectric loss tangent tanδ of the adhesive sheet 10 at 25°C and a frequency of 1000 Hz is 1It is preferably 1.2 or more, and more preferably 1.4 or more. Dielectric loss tangent tanδ 1 (25°C, 1000 Hz) is preferably 1.7 or less, more preferably 1.6 or less.

[0135] From the viewpoint of the drop impact resistance, the dielectric loss tangent tanδ of the adhesive sheet 10 at 25°C and a frequency of 10000 Hz is 2 It is preferably 1.3 or more, and more preferably 1.4 or more. Dielectric loss tangent tanδ 2 (25°C, 10000 Hz) is preferably 1.7 or less, more preferably 1.6 or less.

[0136] From the perspective of ensuring the above drop impact resistance, the dielectric loss tangent tanδ 1 Relative to dielectric loss tangent tanδ 2 The ratio (tanδ 1 / tanδ 2 ) is preferably 0.8 or more, more preferably 0.9 or more, and (tan δ 1 / tanδ 2 ) is preferably 1.4 or less, more preferably 1.3 or less.

[0137] The release liner 21 is, for example, a flexible transparent resin film. Examples of the material of the release liner 21 include polyester resins, polyolefin resins, polycarbonate resins, polyethersulfone resins, polyarylate resins, melamine resins, polyamide resins, cellulose resins, and polystyrene resins. Examples of the polyester resin include polyethylene terephthalate (PET), polybutylene terephthalate, and polyethylene naphthalate. Examples of the polyolefin resin include polyethylene, polypropylene, and cycloolefin polymer (COP). From the viewpoint of transparency and strength, the material of the release liner 21 is preferably a polyester resin, and more preferably PET.

[0138] The surface of the adhesive sheet 10 side of the release liner 21 can be subjected to a release treatment with a release treatment agent. As the release treatment, for example, polysiloxane release treatment, long-chain alkyl acrylate release treatment and fluorine-containing release treatment can be cited. As the release treatment, polysiloxane release treatment is preferred from the viewpoint of ease of adjustment of the release force from the adhesive sheet 10.

[0139] From the viewpoint of ensuring the protective function of the adhesive sheet 10, the thickness of the release liner 21 is preferably 5 μm or more, more preferably 10 μm or more, and further preferably 20 μm or more. From the viewpoint of operability, the thickness of the release liner 21 is preferably 200 μm or less, more preferably 150 μm or less, and further preferably 100 μm or less.

[0140] The release liner 22 is a transparent resin film having flexibility. Examples of the material of the release liner 22 include the materials described above as the material of the release liner 21. The material of the release liner 22 is preferably a polyester resin, and more preferably PET, from the viewpoint of transparency and strength.

[0141] In the present embodiment, the surface of the release liner 22 on the adhesive sheet 10 side is subjected to a release treatment with a release treatment agent. As the release treatment, for example, polysiloxane release treatment, long-chain alkyl acrylate release treatment and fluorine-containing release treatment can be cited. As the release treatment, polysiloxane release treatment is preferred from the viewpoint of ease of adjustment of the release force from the adhesive sheet 10.

[0142] From the viewpoint of ensuring the protective function of the adhesive sheet 10, the thickness of the release liner 22 is preferably 5 μm or more, more preferably 10 μm or more, and further preferably 20 μm or more. From the viewpoint of operability, the thickness of the release liner 22 is preferably 200 μm or less, more preferably 150 μm or less, and further preferably 100 μm or less.

[0143] The pressure-sensitive adhesive sheet 10 can be produced, for example, as follows.

[0144] First, prepare a prepolymer composition. Specifically, first, prepare a mixture (liquid state) containing the above-mentioned monofunctional monomers for forming a base polymer and a photopolymerization initiator (first photopolymerization initiator) (prepolymer composition preparation process). Then, by irradiating the mixture with ultraviolet rays, a part of the monofunctional monomers in the mixture is photopolymerized to obtain a prepolymer composition. As light sources for ultraviolet irradiation, for example, ultraviolet LED lamps, black light lamps, high-pressure mercury lamps and metal halide lamps can be listed. In addition, during ultraviolet irradiation, a wavelength cutoff filter for cutting off a part of the wavelength range of light emitted from the light source can be used as needed. During ultraviolet irradiation, the illumination is, for example, 5mW / cm 2 ~200mW / cm 2 The cumulative irradiation light intensity is, for example, 100 mJ / cm 2 ~5000mJ / cm 2 . The ultraviolet irradiation is preferably continued until the viscosity of the composition reaches about 15 Pa·s to about 25 Pa·s. The viscosity is a value measured using a B-type viscometer under the conditions of rotor No. 5, rotor speed 10 rpm and temperature 30°C. The prepolymer composition contains a photopolymer of a monofunctional monomer (the above-mentioned second photopolymerizable polymer) and a monofunctional monomer that has not undergone a polymerization reaction (residual monomer). In addition, the prepolymer composition does not contain a solvent.

[0145] Next, a second photopolymerizable multifunctional compound (crosslinking agent), a photopolymerization initiator (second photopolymerization initiator) and other components as required are added to the prepolymer composition to prepare an adhesive composition (adhesive composition preparation step). Other components include, for example, additional monofunctional monomers (additional monomers), antioxidants, silane coupling agents and rust inhibitors.

[0146] Then, if Figure 4A As shown, a coating 10A is formed between release liners 21 and 22' (coating forming process). Specifically, first, an adhesive composition is applied to the release surface of the release liner 21 to form a coating 10A. As the coating method of the adhesive composition, for example, roller coating, roller lick coating, gravure coating, reverse coating, roller brush, spray coating, dip roller coating, rod coating, blade coating, air knife coating, curtain coating, lip die coating and mouth die coating can be cited. Next, the release surface of the release liner 22' is attached to the coating 10A on the release liner 21. As the release liner 22', for example, a release liner identical to the release liner 22 can be used.

[0147] Then, if Figure 4B As shown, the coating film 10A between the release liners 21 and 22' is irradiated with ultraviolet rays to form a base adhesive sheet 10B (base adhesive sheet forming step). When irradiated with ultraviolet rays, a photopolymerization reaction in a reaction system including a monofunctional monomer (residual monomer, additional monomer) and a second photopolymerizable multifunctional compound (crosslinking agent) is carried out in the coating film, thereby forming a base polymer.

[0148] Then, if Figure 4C As shown, the release liner 22' ( Figure 4B )(peeling process).

[0149] Then, if Figure 4DAs shown, a post-additive component is supplied to the base adhesive sheet 10B (post-additive component supply step). Specifically, a post-additive component solution (not shown) containing a post-additive component and a solvent is applied to the exposed surface of the base adhesive sheet 10B. The post-additive component contains the above-described first photopolymerizable polyfunctional compound and the above-described photopolymerization initiator (third photopolymerization initiator), and may also contain other additives. Examples of other additives include ultraviolet absorbers and antioxidants. In this step, for example, the post-additive component penetrates from the surface of the base adhesive sheet 10B into the base adhesive sheet 10B, and the solvent is vaporized by heating as needed. Before this step, the base polymer already has a crosslinked structure to form the base adhesive sheet 10B. Therefore, due to the vaporization of the solvent in this step, it is not easy to form (substantially does not form) an orange peel-like (yuzu-hada) surface on the base adhesive sheet 10B. In addition, a photocurable adhesive sheet 10 is formed by the base adhesive sheet 10B and the post-additive component. The amount of the first photopolymerizable polyfunctional compound added in this step is as described above. Relative to 100 parts by mass of the base polymer, it is preferably 0.5 part by mass or more, more preferably 2 parts by mass or more, further preferably 5 parts by mass or more, still more preferably 7 parts by mass or more, and preferably 20 parts by mass or less, more preferably 15 parts by mass or less, further preferably 10 parts by mass or less.

[0150] Next, as Figure 4E shown, another release liner 22 is attached to the adhesive sheet 10 (attachment step).

[0151] As described above, an adhesive sheet 10 whose adhesive surface is covered and protected by release liners 21 and 22 can be manufactured. The adhesive sheet 10 formed from a solvent-free adhesive composition is suitable for reducing the environmental load.

[0152] FIG. 5A to FIG. 5C An example of the usage method of the adhesive sheet 10 is shown.

[0153] In this method, first, as Figure 5A shown, the adhesive sheet 10 is attached to a protective glass 51 (first adherend) (attachment step). The protective glass 51 has a first surface 51a and a second surface 51b on the side opposite to the first surface 51a. A printing layer 52 for decoration or light shielding is formed at the edge of the first surface 51a. The printing layer 52 is provided, for example, on the entire edge of the protective glass 51. The protective glass 51 has a height difference (printing height difference) between the first surface 51a and the surface of the printing layer 52. That is, the protective glass 51 is an adherend with a height difference on the surface. In this step, specifically, the uncured adhesive sheet 10 is attached to the area of the surface 51a of the protective glass 51 that includes the printing layer 52. Figure 5A An example of attaching the uncured adhesive sheet 10 to the entire surface 51a of the protective glass 51 is illustratively shown.

[0154] In the laminating process, the adhesive sheet 10 is laminated to the surface with printed height difference of the protective glass 51 in a soft state before photocuring. In addition, as described above, the adhesive sheet 10 before photocuring has at least one followable height difference d of 50 μm or more in the height difference followability test, and the ratio (d / D) of the followable height difference d to the thickness D of the adhesive sheet 10 is 0.4 or more and 0.8 or less. According to such an adhesive sheet 10, good height difference followability can be achieved in the laminating process.

[0155] Then, if Figure 5B As shown, the protective glass 51 is bonded to the member 53 via the adhesive sheet 10 before photocuring on the protective glass 51. The member 53 is, for example, a pixel panel for a display panel, a polarizing film, or a touch panel.

[0156] Then, if Figure 5C As shown, the adhesive sheet 10 is photocured by ultraviolet irradiation. By ultraviolet irradiation, a photopolymerization reaction of the first photopolymerizable multifunctional compound is carried out in the adhesive sheet 10, thereby forming a photopolymer of the first photopolymerizable multifunctional compound. The photopolymerization reaction is carried out around the base polymer (the first photopolymerizable polymer and the second photopolymerizable polymer having a cross-linked structure), so the photopolymer of the first photopolymerizable multifunctional compound is formed while forming an interpenetrating polymer network structure (IPN) with the base polymer. As a result, the adhesive sheet 10 is highly elasticized (photocuring of the adhesive sheet 10). As light sources for ultraviolet irradiation, for example, ultraviolet LED lamps, black light lamps, high-pressure mercury lamps, and metal halide lamps can be listed. In addition, during ultraviolet irradiation, a wavelength cutoff filter for cutting off a portion of the wavelength region of light emitted from the light source can be used. During ultraviolet irradiation, the illumination is, for example, 5 mW / cm 2 ~200mW / cm 2 The cumulative irradiation light intensity is, for example, 50 mJ / cm 2 ~10000mJ / cm 2 .

[0157] The adhesive sheet 10 is used as described above, for example. The adhesive strength B1 of the adhesive sheet 10 in the first pulling test (adhesive strength of the adhesive sheet 10 after photocuring) is 1.5 MPa or more. When the protective glass 51 and the member 53 are bonded together using such an adhesive sheet 10, good bonding reliability can be achieved.

[0158] Example

[0159] Hereinafter, the present invention will be specifically described by showing the embodiments. However, the present invention is not limited to the embodiments. In addition, the specific numerical values ​​of the following described amounts (contents), physical property values, parameters, etc. can be replaced by the upper limit (defined as the numerical value of "below" or "less than") or the lower limit (defined as the numerical value of "above" or "greater than") of the amounts (contents), physical property values, parameters, etc. corresponding to them described in the above-mentioned "Specific Embodiments".

[0160] <Preparation of acrylic oligomer>

[0161] First, in a reaction vessel having a stirrer, a thermometer, a reflux condenser and a nitrogen inlet tube, a mixture containing 60 parts by mass of tetrahydrodicyclopentadienyl methacrylate (DCPMA), 40 parts by mass of methyl methacrylate (MMA), 3.5 parts by mass of α-thioglycerol as a chain transfer agent and 100 parts by mass of toluene as a polymerization solvent was stirred for 1 hour at 70°C under a nitrogen atmosphere. Next, 0.2 parts by mass of 2,2'-azobisisobutyronitrile (AIBN) as a thermal polymerization initiator was added to the mixture to prepare a reaction solution, which was reacted at 70°C for 2 hours under a nitrogen atmosphere and then at 80°C for 2 hours (polymerization reaction). Next, the reaction solution was heated at 130°C to volatilize and remove toluene, chain transfer agent and unreacted monomers. Thus, an acrylic oligomer (solid) was obtained. The weight average molecular weight of the acrylic oligomer was 5100.

[0162] [Example 1]

[0163] <Preparation of Prepolymer Composition>

[0164] In a flask, a total of 0.062 parts by mass of two first photopolymerization initiators were added to a monomer mixture of 71 parts by mass of n-butyl acrylate (BA), 13 parts by mass of N-vinyl-2-pyrrolidone (NVP), 3 parts by mass of acryloyl morpholine (ACMO) and 13 parts by mass of 4-hydroxybutyl acrylate (4HBA), and then the mixture was irradiated with ultraviolet rays under a nitrogen atmosphere, thereby polymerizing a part of the monomer components in the mixture to obtain a prepolymer composition. The molecular weight between entanglement points of n-butyl acrylate (BA) is 15,000. As the first photopolymerization initiator, 0.031 parts by mass of "Omnirad 184" (1-hydroxycyclohexyl phenyl ketone) manufactured by BASF and 0.031 parts by mass of "Omnirad 651" (2,2-dimethoxy-2-phenylacetophenone) manufactured by BASF were used. Ultraviolet irradiation was continued until the viscosity of the composition reached about 20 Pa·s. The viscosity is a value measured by a B-type viscometer under the conditions of rotor No. 5, rotor speed of 10 rpm and temperature of 30° C. The obtained prepolymer composition is a partial polymer containing a photopolymer (photopolymerizable polymer P1a) and monomer components that have not undergone polymerization reaction (residual monomers).

[0165] <Preparation of Adhesive Composition>

[0166] Next, 100 parts by mass of the prepolymer composition, 10 parts by mass of 2-ethylhexyl (meth)acrylate (2EHA) as an additional monomer, 3 parts by mass of the acrylic oligomer, 0.6 parts by mass of urethane acrylate oligomer (UAO) (trade name "UN-350", manufactured by Negami Industries) as a second photopolymerizable multifunctional compound, 0.4 parts by mass of a second photopolymerization initiator, 0.5 parts by mass of an antioxidant (trade name "Irganox 1010", manufactured by BASF), 0.2 parts by mass of a rust inhibitor (trade name "BT-120", 1,2,3-benzotriazole, manufactured by Johoku Chemical Industry Co., Ltd.), and 0.3 parts by mass of a silane coupling agent (trade name "KBM-403", manufactured by Shin-Etsu Chemical Industry Co., Ltd.) were mixed to obtain an adhesive composition. The molecular weight between entanglement points of 2EHA is 39,000. The amount of the second photopolymerizable polyfunctional compound (crosslinking agent) was 0.55 parts by mass based on 100 parts by mass of the monomer component. As the second photopolymerization initiator, "Omnirad 819" (bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide) manufactured by BASF was used.

[0167] <Production of Base Adhesive Sheet>

[0168] Next, the adhesive composition was applied to the release-treated surface of a first release liner (trade name "Diafoil MRF", thickness 75 μm, manufactured by Mitsubishi Chemical Corporation) having a release-treated surface on one side, thereby forming a coating film. Next, the release-treated surface of a second release liner (trade name "Diafoil MRE", thickness 75 μm, manufactured by Mitsubishi Chemical Corporation) having a release-treated surface on one side was attached to the coating film on the first release liner. Next, the coating film between the release liners was irradiated with ultraviolet rays from the side of the second release liner to photocure the coating film, thereby forming an adhesive layer with a thickness of 100 μm (ultraviolet irradiation process). During the ultraviolet irradiation, a black light lamp (wavelength 320 nm to 400 nm, manufactured by Toshiba) was used as the light source, and the illumination was set to 6.5 mW / cm 2 , set the cumulative irradiation light intensity to 1500mJ / cm 2 . In the ultraviolet irradiation process, a photopolymerization reaction is carried out in the coating film in a reaction system containing the above-mentioned residual monomers, additional monomers and a second photopolymerizable multifunctional compound (cross-linking agent), thereby forming a photopolymerized polymer P1b having a cross-linked structure. In addition, the photopolymerization reaction is carried out around the photopolymerized polymer P1a, so the photopolymerized polymer P1b is formed around the photopolymerized polymer P1a. The adhesive layer formed in this process contains such photopolymerized polymer P1a and photopolymerized polymer P1b as the base polymer P1. By the above operation, a base adhesive sheet with release liners on both sides (first release liner / base adhesive sheet (thickness 100μm) / second release liner) was prepared.

[0169] <Preparation of post-addition component solution>

[0170] 6.0 parts by mass of trimethylolpropane triacrylate (TMPTA) (trade name "Viscoat #295", manufactured by Osaka Organic Chemical Industry Co., Ltd.) as the first photopolymerizable multifunctional compound, 1.2 parts by mass of ethoxylated bisphenol A diacrylate (BPAEODE) (trade name "ABE-300", manufactured by Shin-Nakamura Chemical Industry Co., Ltd.) as another first photopolymerizable multifunctional compound, 0.3 parts by mass of the third photopolymerization initiator, 7.0 parts by mass of an ultraviolet absorber (trade name "Tinosorb S", manufactured by BASF) and 85.5 parts by mass of ethyl acetate as a solvent were mixed to prepare a post-addition component solution (the post-addition component is the component other than the solvent in the solution). As the third photopolymerization initiator, "Omnirad 819" manufactured by BASF was used. The composition of the post-addition component solution is shown in Table 1. In Table 1, the unit of the amount of each component is a relative "part by mass".

[0171] <Production of Optical Adhesive Sheet>

[0172] First, after peeling off the second release liner from the above-mentioned base adhesive sheet with a release liner, the post-addition component solution is applied to the exposed surface of the base adhesive sheet exposed thereby with a thickness of 20 μm (coating treatment). The coating is performed using a rod coater RDS No.10 manufactured by RDSPECIALTIES. Then, the coating is dried in a dryer at 110°C for 60 seconds. Through the coating treatment and the drying treatment, the post-addition components (the first photopolymerizable multifunctional compound, the third photopolymerization initiator, and the ultraviolet absorber) are infiltrated into the base adhesive sheet, and the solvent is vaporized. By infiltrating the post-addition components into the base adhesive sheet, a photocurable optical adhesive sheet is formed. Relative to 100 parts by mass of the prepolymer composition, the addition amount of TMPTA is 6.0 parts by mass, the addition amount of BPAEODE is 1.2 parts by mass, the addition amount of the third photopolymerization initiator (Omnirad 819) is 0.3 parts by mass, and the addition amount of the ultraviolet absorber (Tinosorb S) is 7.0 parts by mass (in Table 2, for the first photopolymerizable multifunctional compound, the amount relative to 100 parts by mass of the monomer component is shown in parentheses). Next, the release-treated surface of a third release liner (trade name "Diafoil MRE", thickness 75 μm, manufactured by Mitsubishi Chemical Corporation) having a release-treated surface on one side was attached to the adhesive sheet on the first release liner.

[0173] By the above operation, a pressure-sensitive adhesive sheet with a release liner (first release liner / pressure-sensitive adhesive sheet (thickness 100 μm) / third release liner) of Example 1 was prepared. The pressure-sensitive adhesive sheet was a photocurable optical pressure-sensitive adhesive sheet comprising a base polymer, a first photopolymerizable multifunctional compound (TMPTA, BPAEODE) and a third photopolymerization initiator.

[0174] [Example 2]

[0175] A PSA sheet with a release liner of Example 2 was prepared in the same manner as the PSA sheet with a release liner of Example 1 except for the following contents: In the preparation of the PSA composition, the blending amount of 2EHA was set to 20 parts by mass.

[0176] [Example 3]

[0177] A PSA sheet with a release liner of Example 3 was prepared in the same manner as the PSA sheet with a release liner of Example 1 except for the following contents. In the preparation of the PSA composition, the blending amount of 2EHA was set to 30 parts by mass.

[0178] [Example 4]

[0179] The adhesive sheet with release liner of Example 4 was prepared in the same manner as the adhesive sheet with release liner of Example 1 except for the following contents. In the preparation of the adhesive composition, the amount of 2EHA was set to 20 parts by mass. In the preparation of the post-addition component solution, BPAEODE was not used, and the amount of ethyl acetate was set to 86.7 parts by mass. In the adhesive sheet of Example 4, the amount of TMPTA added as the second photopolymerizable multifunctional compound was 6.0 parts by mass, and the amount of the third photopolymerization initiator (Omnirad 819) was 0.3 parts by mass relative to 100 parts by mass of the prepolymer composition.

[0180] [Example 5]

[0181] In addition to the following contents, the same operation as the adhesive sheet with release liner of Example 1 was performed to prepare the adhesive sheet with release liner of Example 5. In the preparation of the adhesive composition, the amount of 2EHA was set to 20 parts by mass. In the preparation of the post-addition component solution, the amount of TMPTA was set to 4.0 parts by mass, the amount of BPAEODE was set to 1.2 parts by mass, and the amount of ethyl acetate was set to 87.5 parts by mass. In the adhesive sheet of Example 5, relative to 100 parts by mass of the prepolymer composition, the amount of TMPTA added was 4.0 parts by mass, the amount of BPAEODE added was 1.2 parts by mass, and the amount of the third photopolymerization initiator (Omnirad 819) added was 0.3 parts by mass.

[0182] [Example 6]

[0183] In addition to the following contents, the same operation as the adhesive sheet with release liner of Example 1 was performed to prepare the adhesive sheet with release liner of Example 6. In the preparation of the adhesive composition, the amount of 2EHA was set to 20 parts by mass. In the preparation of the post-addition component solution, the amount of TMPTA was set to 2.0 parts by mass, the amount of BPAEODE was set to 1.2 parts by mass, and the amount of ethyl acetate was set to 89.5 parts by mass. In the adhesive sheet of Example 6, relative to 100 parts by mass of the prepolymer composition, the amount of TMPTA added was 2.0 parts by mass, the amount of BPAEODE added was 1.2 parts by mass, and the amount of the third photopolymerization initiator (Omnirad 819) added was 0.3 parts by mass.

[0184] [Comparative Example 1]

[0185] A PSA sheet with a release liner of Comparative Example 1 was prepared in the same manner as the PSA sheet with a release liner of Example 1 except for the following matters: 2EHA was not used in the preparation of the PSA composition.

[0186] [Comparative Example 2]

[0187] The adhesive sheet with release liner of Comparative Example 2 was prepared in the same manner as the adhesive sheet with release liner of Comparative Example 1 except for the following contents. In the preparation of the post-addition component solution, BPAEODE was not used, and the amount of ethyl acetate was set to 86.7 parts by mass. In the adhesive sheet of Comparative Example 2, the amount of TMPTA added as the second photopolymerizable multifunctional compound was 6.0 parts by mass, and the amount of the third photopolymerization initiator (Omnirad 819) was 0.3 parts by mass relative to 100 parts by mass of the prepolymer composition.

[0188] [Comparative Example 3]

[0189] The adhesive sheet with release liner of Comparative Example 3 was prepared in the same manner as the adhesive sheet with release liner of Comparative Example 1 except for the following contents. In the preparation of the post-addition component solution, the amount of TMPTA was set to 4.0 parts by mass, BPAEODE was not used, and the amount of ethyl acetate was set to 88.7 parts by mass. In the adhesive sheet of Comparative Example 3, the amount of TMPTA added as the second photopolymerizable multifunctional compound was 4.0 parts by mass, and the amount of the third photopolymerization initiator (Omnirad 819) was 0.3 parts by mass relative to 100 parts by mass of the prepolymer composition.

[0190] [Comparative Example 4]

[0191] The adhesive sheet with release liner of Comparative Example 4 was prepared in the same manner as the adhesive sheet with release liner of Comparative Example 1 except for the following contents. In the preparation of the post-addition component solution, the amount of TMPTA was set to 2.0 parts by mass, BPAEODE was not used, and the amount of ethyl acetate was set to 90.7 parts by mass. In the adhesive sheet of Comparative Example 4, the amount of TMPTA added as the second photopolymerizable multifunctional compound was 2.0 parts by mass, and the amount of the third photopolymerization initiator (Omnirad 819) was 0.3 parts by mass relative to 100 parts by mass of the prepolymer composition.

[0192] [Comparative Example 5]

[0193] The adhesive sheet with release liner of Comparative Example 5 was prepared in the same manner as the adhesive sheet with release liner of Example 1 except for the following contents. 2EHA was not used in the preparation of the adhesive composition. In the ultraviolet irradiation process for preparing the base adhesive sheet, ultraviolet irradiation (first irradiation) using a black light lamp (wavelength 320nm to 400nm, manufactured by Toshiba) and then ultraviolet irradiation (second irradiation) using an ultraviolet LED lamp (wavelength 365nm, manufactured by Quark Technology) were performed. In the first irradiation, the illumination was set to 6.5mW / cm 2, set the cumulative irradiation light intensity to 1500mJ / cm 2 In the second irradiation, the illuminance was set to 90 mW / cm 2 , set the cumulative irradiation light intensity to 1800mJ / cm 2 . Through such an ultraviolet irradiation process, a base polymer P2 having a weight average molecular weight (Mw) smaller than that of the above-mentioned base polymer P1 is formed. In addition, in the preparation of the post-addition component solution, BPAEODE is not used, and the amount of ethyl acetate is set to 86.7 parts by mass. In the adhesive sheet of Comparative Example 5, the amount of TMPTA added as the second photopolymerizable multifunctional compound is 6.0 parts by mass, and the amount of the third photopolymerization initiator (Omnirad 819) added is 0.3 parts by mass relative to 100 parts by mass of the prepolymer composition.

[0194] [Comparative Example 6]

[0195] The adhesive sheet with release liner of Comparative Example 6 was prepared in the same manner as the adhesive sheet with release liner of Comparative Example 5 except for the following contents. In the preparation of the post-addition component solution, the amount of TMPTA was set to 4.0 parts by mass, BPAEODE was not used, and the amount of ethyl acetate was set to 88.7 parts by mass. In the adhesive sheet of Comparative Example 6, the amount of TMPTA added as the second photopolymerizable multifunctional compound was 4.0 parts by mass, and the amount of the third photopolymerization initiator (Omnirad 819) was 0.3 parts by mass relative to 100 parts by mass of the prepolymer composition.

[0196] [Comparative Example 7]

[0197] The adhesive sheet with release liner of Comparative Example 7 was prepared in the same manner as the adhesive sheet with release liner of Comparative Example 5 except for the following contents. In the preparation of the post-addition component solution, the amount of TMPTA was set to 2.0 parts by mass, BPAEODE was not used, and the amount of ethyl acetate was set to 90.7 parts by mass. In the adhesive sheet of Comparative Example 7, the amount of TMPTA added as the second photopolymerizable multifunctional compound was 2.0 parts by mass, and the amount of the third photopolymerization initiator (Omnirad 819) was 0.3 parts by mass relative to 100 parts by mass of the prepolymer composition.

[0198] <Measurement of Weight Average Molecular Weight>

[0199] The weight average molecular weight (Mw) of each of the acrylic polymer and acrylic oligomer was measured by gel permeation chromatography (GPC) under the following measurement conditions, and was obtained as a polystyrene conversion value. In the measurement, a GPC measuring apparatus (trade name "HLC-8120GPC", manufactured by Tosoh) was used. The sample solution was prepared as follows.

[0200] First, a dimethylformamide (DMF) solution (with salt added) with a sample concentration of 0.20 mass % was prepared using an acrylic acid oligomer as a sample, and the DMF solution was left to stand for 20 hours. Next, the DMF solution was filtered using a membrane filter with an average pore size of 0.45 μm, and the obtained filtrate was used as a sample solution for molecular weight measurement.

[0201] [GPC measurement conditions]

[0202] Column: Super AWM-H + SuperAW 4000 + SuperAW 2500, each TSKgel (manufactured by Tosoh)

[0203] Column temperature: 40°C

[0204] Eluent: DMF solution (with added salt)

[0205] Flow rate: 0.4 mL / min

[0206] Sample injection volume: 40μL

[0207] Standard sample: Polystyrene (manufactured by Agilent)

[0208] Detector: Differential Refractometer (RI)

[0209] <Light transmittance>

[0210] For each adhesive sheet of Examples 1 to 6 and Comparative Examples 1 to 7, the transmittance was measured by the following operation. First, a sample for transmittance measurement was prepared. Specifically, the third release liner was peeled off from the adhesive sheet, and then the exposed surface of the adhesive sheet was attached to the alkali-free glass (manufactured by Matsunami Glass Co., Ltd.), and the liner glass was peeled off from the adhesive sheet on the glass. A sample for measurement was thus obtained. Next, the transmittance of the adhesive sheet in the sample was measured using a spectrophotometer (trade name "U 4100", manufactured by Hitachi High-Tech). In addition, in this measurement, the measurement results obtained by measuring only the alkali-free glass under the same conditions were used as the baseline. The transmittance R1 at a wavelength of 380nm and the transmittance R2 at a wavelength of 420nm measured for the adhesive sheet are shown in Tables 2 and 3.

[0211] <Height difference tracking performance>

[0212] The step followability of each of the PSA sheets of Examples 1 to 6 and Comparative Examples 1 to 7 was examined in the following manner.

[0213] First, a sample sheet (75 mm long × 45 mm wide) was cut out from the adhesive sheet with a release liner. Then, the third release liner was peeled off from the adhesive sheet in the sample sheet, and the exposed surface of the adhesive sheet thus exposed was bonded to the center of a PET film (100 mm long × 50 mm wide, 125 μm thick). During bonding, a roller press was used, and the pressure between the rollers was set to 0.2 MPa, and the feed speed was set to 100 mm / min. Then, the first release liner was peeled off from the adhesive sheet on the PET film, and the exposed surface of the adhesive sheet thus exposed was bonded to a glass plate (100 mm long × 50 mm wide, 500 μm thick) with a printed layer, thereby obtaining a conjugate (the first conjugate). During bonding, a roller press was used, and the pressure between the rollers was set to 0.2 MPa, and the feed speed was set to 100 mm / min. Figure 2 The figure shows the positional relationship between the glass plate 31, the sample sheet 32 ​​(optical adhesive sheet), and the printed layer 33 in the first bonded body. A printed layer 33 (black ink layer) of a predetermined thickness (45 μm, 50 μm) is formed on one surface of the glass plate 31 in the thickness direction along the entire edge of the glass plate 31. The printed layer 33 is formed within a range of 15 mm from each end of the glass plate 31 in the length direction L1, and within a range of 5 mm from each end of the glass plate 31 in the width direction L2 (within 1 mm). Figure 2 In the figure, hatching is indicated to indicate the printed layer 33). The sample sheet 32 ​​is attached to the center of one surface in the thickness direction of the glass plate 31, and the entire edge of the sheet is in contact with the printed layer 33. That is, the printed layer 33 on the glass plate 31 is sandwiched between the glass plate 31 and the adhesive sheet 32 ​​within a range of 2.5 mm from the inner end of the layer to the outer side.

[0214] Next, the first bonded body was subjected to autoclave treatment at 50°C, 0.5 MPa, and 15 minutes. Next, ultraviolet rays were irradiated from the glass plate 31 side to the sample piece 32 on the glass plate 31, thereby photocuring the sample piece 32. During the ultraviolet irradiation, a metal halide lamp was used as a light source, and the illumination was set to 300 mW / cm 2 , set the cumulative irradiation light intensity to 3000mJ / cm 2. Then, the vicinity of the inner end edge of the printed layer 33 in the first bonded body was observed. Specifically, the inner side of the inner end edge of the printed layer 33 (the area where the sample sheet 32 ​​should be adhered to the glass plate 31) was observed from the PET film side of the first bonded body using a digital microscope at an observation magnification of 20. As a result, when the thickness of the printed layer was 45 μm, no bubbles were confirmed within the observation range in each adhesive sheet (thickness 100 μm) of Examples 1 to 6 and Comparative Examples 1 to 7. When the thickness of the printed layer was 50 μm, no bubbles were confirmed within the observation range in each adhesive sheet (thickness 100 μm) of Examples 1 to 6 and Comparative Examples 5 to 7, and bubbles were confirmed within the observation range in each adhesive sheet (thickness 100 μm) of Comparative Examples 1 to 4. That is, the ratio (d / D) of the height difference d that can be followed by each adhesive sheet of Examples 1 to 6 and Comparative Examples 5 to 7 relative to the thickness D of the adhesive sheet is 0.5, and the ratio (d / D) of the height difference d that can be followed by each adhesive sheet of Comparative Examples 1 to 4 relative to the thickness D of the adhesive sheet is 0.45. Moreover, regarding the height difference followability of the adhesive sheet, when the thickness of the printed layer is 50 μm, the case where no bubbles are confirmed within the observation range is evaluated as "excellent", and the case where bubbles are confirmed is evaluated as "poor". These results are shown in Tables 2 and 3.

[0215] <Pull test>

[0216] The adhesive strength of each of the PSA sheets in Examples 1 to 6 and Comparative Examples 1 to 7 was measured by the following pull test.

[0217] First, a test sample is prepared for each adhesive sheet. In the preparation of the test sample, first, the third release liner of the adhesive sheet small piece (10mm×10mm) cut out from the adhesive sheet with a release liner is peeled off, and the exposed surface exposed thereby is bonded to an alkali glass plate (first alkali glass plate). Next, the first release liner is peeled off from the adhesive sheet on the alkali glass plate, and the exposed surface exposed thereby is bonded to another alkali glass plate (second alkali glass plate), thereby bonding the glass plates to each other. Thus, a bonded body (second bonded body) is obtained in which the first alkali glass plate and the second alkali glass plate are bonded in the thickness direction via the adhesive sheet small piece. Next, the second bonded body is heat-treated under the conditions of a temperature of 50°C, a pressure of 0.5MPa and 15 minutes, so that the adhesive sheet small piece is pressed onto the two glass plates. Next, the adhesive sheet between the glass plates in the second bonded body is photocured by ultraviolet irradiation. During the ultraviolet irradiation, a metal halide lamp is used as the light source, and the illumination is set to 300mW / cm 2 , set the cumulative irradiation light intensity to 3000mJ / cm 2 By the above operation, a sample for measurement (first alkali glass plate / adhesive sheet small piece / second alkali glass plate) was prepared. Figure 3 As shown, the measurement sample (second bonded body) W includes a first alkali glass plate 41 , an adhesive sheet 10 , and a second alkali glass plate 42 in this order in the thickness direction H. The adhesive sheet 10 bonds the first alkali glass plate 41 and the second alkali glass plate.

[0218] Next, a test was performed in which the two alkali glass plates in the test sample were pulled toward opposite sides in the thickness direction to measure the force required to pull the glass plates apart (first pulling test). A tensile testing machine (product name "Autograph AG-50NX plus", manufactured by Shimadzu Corporation) was used in this measurement. In this measurement, the measurement temperature was set to 85°C, the relative humidity was set to 55%, and the pulling speed was set to 25 mm / min. The maximum value of the measured force is shown in Tables 2 and 3 as the adhesive strength B1 (MPa) at 85°C.

[0219] The tensile test was carried out in the same manner as the first tensile test except that the measurement temperature was set to 25°C instead of 85°C, and the force required to pull the glass plates apart was measured (second tensile test). The maximum value of the measured force is shown in Tables 2 and 3 as the adhesive strength B2 (MPa) at 25°C. The ratio of the adhesive strength B2 to the adhesive strength B1 (B2 / B1) is also shown in Tables 2 and 3.

[0220] The tensile test was carried out in the same manner as the first tensile test except that the measurement temperature was set to -20°C instead of 85°C, and the force required to pull the glass plates apart was measured (third tensile test). The maximum value of the measured force is shown in Tables 2 and 3 as the adhesive strength B3 (MPa) at -20°C. The ratio of the adhesive strength B3 to the adhesive strength B1 (B3 / B1) is also shown in Tables 2 and 3.

[0221] <Dynamic viscoelasticity measurement>

[0222] The dynamic viscoelasticity of each of the PSA sheets of Examples 1 to 6 and Comparative Examples 1 to 7 was measured.

[0223] First, a necessary number of samples for each adhesive sheet were prepared. Specifically, a plurality of small pieces of adhesive sheets cut out from the adhesive sheet were bonded together to prepare a sample sheet of about 1 mm thick. Next, the sheet was punched to obtain a cylindrical pellet (7.9 mm in diameter) as a sample for the measurement.

[0224] Next, for the sample to be measured, a dynamic viscoelasticity measurement was performed using a dynamic viscoelasticity measuring device (trade name "Advanced Rheological Expansion System (ARES) G2", manufactured by TA Instruments). Specifically, the sample to be measured was fixed to the fixture of the parallel plate with a diameter of 7.9 mm of the device, and then the measurement was performed. In this measurement, the measurement mode was set to the shear mode, the strain was set to 0.3%, the measurement temperature was set to every 5°C in the range of -50°C to 150°C, and the angular frequency range was set to 0.01 rad / second to 100 rad / second. Next, using the analysis software built into the dynamic viscoelasticity measuring device, the reference temperature was set to 25°C, and the frequency range of 1.0×10 -7 Hz~1×10 9 Hz master curve (synthetic curve). Thus, the frequency dependence data of shear storage modulus G' and dielectric loss tangent tanδ (= shear loss modulus G" / shear storage modulus G') were obtained. Then, the dielectric loss tangent tanδ at a frequency of 1000Hz was read from the obtained data. 1 , Dielectric loss tangent tanδ at frequency 10000Hz 2 、The minimum value of dielectric loss tangent tanδ at frequency 1000Hz~10000Hz V min and maximum value V max These values ​​are shown in Table 2 and Table 3. Dielectric loss tangent tanδ 1 Relative to dielectric loss tangent tanδ 2 The ratio (tanδ 1 / tanδ 2 ) are also shown in Tables 2 and 3. In addition, the temperature at which the dielectric loss tangent tanδ reaches a maximum value is read within the measurement temperature range. This value is shown in Tables 2 and 3 as the glass transition temperature Tg (° C.) of the adhesive sheet.

[0225] <Drop impact resistance>

[0226] The drop impact resistance of each of the PSA sheets of Examples 1 to 6 and Comparative Examples 1 to 7 was examined in the following manner.

[0227] First, a joint body (third joint body) for evaluation was prepared. Specifically, first, a rectangular sample piece (75 mm long × 45 mm wide) was cut out from an adhesive sheet with a release liner. Next, the third release liner was peeled off from the adhesive sheet in the sample piece, and the exposed surface of the adhesive sheet thus exposed was bonded to the center of a rectangular first glass plate (100 mm long × 75 mm wide, 500 μm thick) along four sides. During bonding, a roller press was used, the pressure between the rollers was set to 0.2 MPa, and the feed speed was set to 100 mm / min. Next, the adhesive sheet on the first glass plate was photocured by ultraviolet irradiation. During ultraviolet irradiation, a metal halide lamp was used as the light source, and the illumination was set to 300 mW / cm 2 , set the cumulative irradiation light intensity to 3000mJ / cm 2 . Next, the first release liner is peeled off from the adhesive sheet on the first glass plate, and the exposed surface of the adhesive sheet thus exposed is bonded to the center of a rectangular second glass plate (length 100mm×width 50mm, thickness 500μm) with a printed layer by vacuum pressing (surface pressure 0.3MPa, pressure 100Pa) along four sides, thereby obtaining a third joint body. A printed layer (thickness 30μm, black ink layer) is formed on the entire end edge of the second glass plate on one surface in the thickness direction of the second glass plate. The printed layer is formed within a range of 15mm inward from each end of the second glass plate in the length direction and within a range of 5mm inward from each end of the second glass plate in the width direction. The adhesive sheet is bonded to the center of one surface in the thickness direction of such a second glass plate and contacts the printed layer on the entire end edge of the sheet. That is, the printed layer on the second glass plate is sandwiched between the second glass plate and the adhesive sheet within a range of 2.5mm from the inner end of the layer to the outer side. Next, the third bonded body was subjected to a heat treatment (autoclaving) under the conditions of 50° C., 0.5 MPa, and 30 minutes.

[0228] Using the third joint body produced as described above, a drop impact resistance test was carried out as follows. First, a joint body was placed on a specified support table. Specifically, the joint body was placed on a support table in a manner such that the first glass plate in the joint body was located on the upper side and both ends of the first glass plate in the width direction were supported by the support table from below (the second glass plate on the lower side was not in contact with the support table). Next, the joint body on the support table was fixed to the support table using an adhesive tape. Next, the support table and the joint body were kept at -5°C for 24 hours. Next, within 40 seconds after the support table and the joint body were restored to room temperature, a metal ball was dropped toward the joint body on the support table so that the metal ball collided with the first glass plate of the joint body. The mass of the metal ball was 30g, and the drop height of the metal ball was 300mm. In addition, the falling position of the metal ball relative to the joint body was a position more than 10mm away from the printed layer in the length direction and the width direction, respectively. Two tests (tests of different samples) (n=2) were carried out on each adhesive sheet. Then, regarding the drop impact resistance of the adhesive sheet, the case where no peeling between the first glass plate and the second glass plate occurred in any test was evaluated as "excellent", the case where peeling between the first glass plate and the second glass plate occurred only in one test was evaluated as "acceptable", and the case where peeling between the first glass plate and the second glass plate occurred in any test was evaluated as "poor". The results are shown in Tables 2 and 3.

[0229]

[0230]

[0231]

[0232] It should be noted that the above invention is provided as an exemplary embodiment of the present invention, but this is merely an example and should not be interpreted as limiting. Modifications of the present invention that are obvious to those skilled in the art are included in the scope of the claims.

[0233] Industrial Applicability

[0234] The optical adhesive sheet of the present invention is suitably used in, for example, production of a display panel.

Claims

1. An optical adhesive sheet, wherein: The optical adhesive sheet comprises a base polymer, a photopolymerizable multifunctional compound and a photopolymerization initiator. The optical adhesive sheet has at least one followable height difference d of 50 μm or more in the following height difference followability test, and the ratio of the followable height difference d to the thickness D of the optical adhesive sheet is 0.4 or more and 0.8 or less, The adhesive strength B1 in the first tensile test described below is 1.5 MPa or more, Height difference tracking test: First, a glass plate (length 100 mm×width 50 mm) having a first surface and a second surface opposite to the first surface, a polyethylene terephthalate film (length 100 mm×width 50 mm), and a sample sheet of the optical adhesive sheet (length 75 mm×width 45 mm) are prepared; a printed layer having a thickness h of 50 μm or more is formed on the first surface of the glass plate over the entire edge of the glass plate; the printed layer is formed within a range of 15 mm inward from each end of the glass plate in the length direction of the glass plate, and within a range of 5 mm inward from each end of the glass plate in the width direction of the glass plate; Next, the first surface side of the glass plate is joined to the polyethylene terephthalate film in the thickness direction via the sample piece arranged at the center of the length direction and the width direction relative to the glass plate, thereby obtaining a first joined body; in the first joined body, the printed layer is sandwiched between the glass plate and the sample piece within a range of 2.5 mm from the inner end of the printed layer to the outer side; Next, the first bonded body is subjected to a heat treatment under the conditions of 50° C., 0.5 MPa, and 15 minutes; Next, the cumulative irradiation light dose was 3000 mJ / cm 2 irradiating the sample sheet in the first joint body with ultraviolet light to photo-cure the sample sheet in the first joint body; Next, the inner side of the inner edge of the printed layer is observed from the polyethylene terephthalate film side of the first bonded body using a digital microscope at an observation magnification of 20, and when no air bubbles are confirmed in the observation range, the thickness h is taken as the trackable height difference d; First pull test: First, the first alkali glass plate and the second alkali glass plate were bonded in the thickness direction via the optical adhesive sheet to obtain a second bonded body; then, the optical adhesive sheet was irradiated with a cumulative light intensity of 3000 mJ / cm 2 The optical adhesive sheet is photocured by ultraviolet irradiation; then, the second bonded body is heat treated under the conditions of 50°C, 0.5 MPa and 15 minutes; then, the first alkali glass plate and the second alkali glass plate in the second bonded body are pulled toward opposite sides of each other in the thickness direction at 85°C and a pulling speed of 25 mm / min, thereby measuring the adhesive strength B1.

2. The optical adhesive sheet according to claim 1, wherein In the second pulling test described below, the adhesive strength B2 is present, and the ratio of the adhesive strength B2 to the adhesive strength B1 is 2.0 or more and 3.5 or less, Second pulling test: First, the first alkali glass plate and the second alkali glass plate were bonded in the thickness direction via the optical adhesive sheet to obtain a third bonded body; then, the accumulated irradiation light amount was 3000 mJ / cm 2 The optical adhesive sheet is photocured by ultraviolet irradiation; then, the third bonded body is heat treated under the conditions of 50°C, 0.5 MPa and 15 minutes; then, the first alkali glass plate and the second alkali glass plate in the third bonded body are pulled toward opposite sides of each other in the thickness direction under the conditions of 25°C and a pulling speed of 25 mm / min, thereby measuring the adhesive strength B2.

3. The optical adhesive sheet according to claim 1, wherein In the third pulling test described below, the adhesive strength B3 is present, and the ratio of the adhesive strength B3 to the adhesive strength B1 is 3.0 or more and 4.2 or less, The third pulling test: First, the first alkali glass plate and the second alkali glass plate were bonded in the thickness direction via the optical adhesive sheet to obtain a fourth bonded body; then, the accumulated irradiation light amount was 3000 mJ / cm 2 The optical adhesive sheet is photocured by ultraviolet irradiation; then, the fourth bonded body is heat treated under the conditions of 50°C, 0.5 MPa and 15 minutes; then, the first alkali glass plate and the second alkali glass plate in the fourth bonded body are pulled toward opposite sides of each other in the thickness direction at -20°C and a pulling speed of 25 mm / min, thereby measuring the adhesive strength B3.

4. The optical adhesive sheet according to any one of claims 1 to 3, wherein The thickness D is greater than or equal to 80 μm.

Citation Information

Patent Citations

  • Adhesive composition, pressure sensitive adhesive double coated tape, adhesion method and portable electronic device

    JP2007051271A

  • Transparent pressure-sensitive adhesive sheet for flat panel display, and flat panel display

    JP2010097070A